Toner for electrostatic image development

By using colored resin particles containing polydiene structural additives in the toner for electrostatic image development, the contradiction between low-temperature fixability and storage stability is solved, and efficient low-temperature fixation and good storage stability are achieved.

CN112602022BActive Publication Date: 2025-02-14ZEON CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201980054447.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-27
Filing Date
2019-08-30
Publication Date
2025-02-14
Estimated Expiration
2039-08-30

AI Technical Summary

Technical Problem

The prior art is inadequate in the storage stability when improving the low-temperature fixability, especially when used at high temperatures or placed for a long time, it is easy to cause toner particles to stick, affecting the storage ability.

Method used

To the toner for electrostatic image development, colored resin particles including a binder resin, a colorant, a charging control agent, a release agent, and an additive having a polydiene structure are added. The toner is optimized by controlling the number of crystal domains of the release agent with a solubility in styrene at a temperature of 40°C and controlling the aspect ratio of the release agent in the colored resin particles with an aspect ratio of 2 to 10. Composition and structure.

Benefits of technology

The high and low temperature fixing and storage stability of the toner are achieved, which reduces energy consumption and avoids the adhesion problem of the toner during high temperature or long-term placement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112602022B_ABST
    Figure CN112602022B_ABST
Patent Text Reader

Abstract

The present invention provides a toner for electrostatic image development, comprising colored resin particles containing a binder resin, a colorant, a charge control agent, a release agent, and an additive having a polydiene structure, wherein the solubility of the additive having a polydiene structure in styrene at a temperature of 40° C. is 3 to 40 g / 100 g, and when a cross section of the colored resin particles is observed through a transmission electron microscope (TEM), in a 2 μm×2 μm square field of view of the cross section of the colored resin particles, the number of crystal domains of the release agent having an aspect ratio in the range of 2 to 10 is 2 to 30.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a toner for developing an electrostatic image, which is used for developing an electrostatic latent image in electrophotography, electrostatic recording, electrostatic printing, and the like. Background Art

[0002] In image forming apparatuses such as electronic photographic apparatuses, electrostatic recording apparatuses, and electrostatic printing apparatuses, a method of forming a desired image by developing an electrostatic latent image formed on a photosensitive body with an electrostatic image developing toner is widely used and is applied to copiers, printers, fax machines, and their multifunction machines.

[0003] For example, in an electronic photographic device using an electrophotographic method, the surface of a photosensitive body formed of a photoconductive material is usually uniformly charged by various methods, and then an electrostatic latent image is formed on the photosensitive body. The electrostatic latent image is then developed using a colorant (development process), and the colorant image is transferred to a recording material such as paper as needed (transfer process). The colorant is then fixed to the recording material by heating or the like (fixing process), thereby obtaining a printed material.

[0004] In the above-mentioned image forming process, especially in the fixing process, it is usually necessary to heat the fixing roller to a temperature of 150°C or more during fixing, and a large amount of electricity as an energy source is consumed. In contrast, in recent years, with the increasing demand for reducing energy consumption and increasing printing speed of the above-mentioned image forming apparatus, it is necessary to design a toner that can maintain a high fixing rate even at a low fixing temperature (toner with excellent low-temperature fixing property).

[0005] In response to the above requirements, methods have been proposed, such as lowering the glass transition temperature (Tg) of the colorant, making the colorant contain a low melting point resin and / or a low molecular weight resin, and making the colorant contain a low softening point substance (release agent) with releasable properties such as wax.

[0006] However, in order to improve the low-temperature fixability, the temperature of the fixing roller can be set low during fixing. However, when the toner is used at high temperature or is placed (stored) for a long time, the toner particles may be easily fused (adhesion (agglomeration)) with each other, and the storage property of the toner is reduced. Therefore, in the design of the toner, the storage property, which is a characteristic opposite to the low-temperature fixability, needs to be considered, and a toner that can improve the low-temperature fixability and reduce power consumption without damaging the storage property is developed.

[0007] For example, Patent Document 1 discloses a black colorant, characterized in that it comprises colorant particles containing a binding resin, a crystalline material and a black colorant, and in a cross section of the colorant particle observed by a transmission electron microscope, when the major axis of the cross section of the colorant particle is R (μm) and the major axis of the crystal domain of the crystalline material is r (μm), and R (μm) satisfies 4≤R≤12, and when the crystal domain of the crystalline material satisfying the following formula (i) is taken as the crystal domain A, the number of the crystal domains A per cross section of the colorant particle is greater than 20 and less than 300.

[0008] (i)5.0×10 -4 ≤r / R≤7.0×10 -2

[0009] According to the technique of Patent Document 1, the crystal domain A melts during heat fixing to plasticize the entire resin, and the crystalline material constituting the crystal domain A seeps out on the surface of the toner particles to improve the fixability and exert the release property from a fixing member such as a fixing film.

[0010] In addition, Patent Document 2 discloses a toner characterized in that it has toner particles containing a binder resin and a colorant, and in the viscoelastic properties measured using a rotating plate rheometer at a frequency of 6.28 rad / sec, the toner has a storage modulus (G'60) of 1.0×10 7 ~1.0×10 9 (Pa), the maximum value of storage modulus (G'p) exists between 110℃ and 140℃, G'p is 5.0×10 4 ~5.0×10 6 (Pa).

[0011] Prior art literature

[0012] Patent Literature

[0013] Patent Document 1: Japanese Patent Application Publication No. 2019-12188;

[0014] Patent document 2: Japanese Patent Application Publication No. 2012-177914. Summary of the invention

[0015] Problem that the invention aims to solve

[0016] On the other hand, in the technology of Patent Document 1, although the fixing properties such as low-temperature fixing property are improved, the storage stability is not sufficient, and further improvement is required.

[0017] Furthermore, the technology of Patent Document 2 uses a polyester-based resin as a binder resin, and has a problem that low-temperature fixability is insufficient.

[0018] An object of the present invention is to provide a toner for developing electrostatic images having excellent storage stability and low-temperature fixing properties.

[0019] Solutions for solving problems

[0020] The present inventors have conducted studies to achieve the above-mentioned object and have found that, in a toner for electrostatic image development containing colored resin particles including a binder resin, a colorant, a charge control agent and a release agent, the above-mentioned problems can be solved by making the colored resin particles contain an additive having a polydiene structure having a solubility of 3 to 40 g / 100 g in styrene at a temperature of 40° C., and by controlling the number of crystal domains of the release agent having an aspect ratio in the range of 2 to 10 in the colored resin particles within a prescribed range, thereby completing the present invention.

[0021] Furthermore, the present inventors have conducted further studies and found that, in a toner for electrostatic image development containing colored resin particles containing a binder resin, a colorant, a charge control agent and a release agent, an additive having a polydiene structure having a solubility of 3 to 40 g / 100 g in styrene at a temperature of 40° C. is contained in the colored resin particles as an additive, and the storage modulus G'(60) of the colored resin particles at 60° C. determined by dynamic viscoelasticity measurement is controlled within 1.6×10 8 ~5.0×10 8 The range of Pa can also solve the above problems.

[0022] That is, according to the present invention, as a toner for electrostatic image development according to a first aspect, there is provided a toner for electrostatic image development, which contains colored resin particles, wherein the colored resin particles contain a binder resin, a colorant, a charge control agent, a release agent, and an additive having a polydiene structure,

[0023] The solubility of the additive having a polydiene structure in styrene at a temperature of 40° C. is 3 to 40 g / 100 g.

[0024] When the cross section of the colored resin particles is observed by a transmission electron microscope (TEM), the number of crystal domains of the release agent having an aspect ratio in the range of 2 to 10 is 2 to 30 in a 2 μm×2 μm square field of view of the cross section of the colored resin particles.

[0025] Alternatively, according to the present invention, as a second aspect of an electrostatic image developing toner, there is provided an electrostatic image developing toner comprising colored resin particles, wherein the colored resin particles contain a binder resin, a colorant, a charge control agent, a release agent, and an additive having a polydiene structure,

[0026] The solubility of the additive having a polydiene structure in styrene at a temperature of 40° C. is 3 to 40 g / 100 g.

[0027] The storage modulus G'(60) of the colored resin particles at 60°C obtained by dynamic viscoelasticity measurement is 1.6×10 8 ~5.0×10 8 Pa.

[0028] In the electrostatic image developing toner according to the second aspect of the present invention, it is preferred that the storage modulus G'(100) of the colored resin particles at 100° C. determined by dynamic viscoelasticity measurement is 1.0×10 5 ~3.0×10 5 Pa.

[0029] In the electrostatic image developing toner according to the second aspect of the present invention, it is preferred that the ratio of the storage modulus G'(60) at 60°C to the storage modulus G'(100) at 100°C (G'(60) / G'(100) of the colored resin particles determined by dynamic viscoelasticity measurement is 1.0×10 3 ~5.0×10 3 .

[0030] In the electrostatic image developing toner of the present invention, it is preferred that the additive having a polydiene structure is an aromatic vinyl-based thermoplastic elastomer.

[0031] Alternatively, in the electrostatic image developing toner of the present invention, the conjugated diene-aromatic vinyl-based thermoplastic elastomer preferably contains 40% by mass or more of a diblock copolymer composed of an aromatic vinyl polymer block and a polymer block copolymerizable with the aromatic vinyl polymer.

[0032] In the electrostatic image developing toner of the present invention, the content ratio of the aromatic vinyl monomer unit in the conjugated diene-aromatic vinyl-based thermoplastic elastomer is preferably 10 to 30% by mass based on the total monomer units.

[0033] In the electrostatic image developing toner of the present invention, it is preferred that the content of the additive having a polydiene structure is 1 to 10 parts by mass based on 100 parts by mass of the binder resin.

[0034] Furthermore, in the electrostatic image developing toner of the present invention, it is preferred that the release agent is a fatty acid ester compound having a number average molecular weight (Mn) of 500 to 1500.

[0035] Effects of the Invention

[0036] According to the present invention, it is possible to provide a toner for developing electrostatic images which is excellent in storage stability and low-temperature fixing property. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 (A) is a cross-sectional photograph of the colored resin particles in Example 1-1 obtained by a transmission electron microscope (TEM), Figure 1 (B) is a cross-sectional photograph of the colored resin particles in Comparative Example 1-1 obtained by a transmission electron microscope (TEM). DETAILED DESCRIPTION

[0038] <Toner for Electrostatic Image Development of the First Aspect>

[0039] A toner for electrostatic image development according to a first aspect of the present invention (hereinafter, sometimes simply referred to as "toner") comprises colored resin particles, wherein the colored resin particles contain a binder resin, a colorant, a charge control agent, a release agent, and an additive having a polydiene structure.

[0040] The solubility of the additive having a polydiene structure in styrene at a temperature of 40° C. is 3 to 40 g / 100 g.

[0041] When a cross section of the colored resin particles is observed by a transmission electron microscope (TEM), the number of crystal domains of the release agent having an aspect ratio in the range of 2 to 10 is in the range of 2 to 30 in a 2 μm×2 μm square field of view of the cross section of the colored resin particles.

[0042] First, a method for producing colored resin particles constituting a toner according to a first aspect of the present invention will be described.

[0043] The method for producing the colored resin particles constituting the toner of the first aspect of the present invention is roughly divided into dry methods such as pulverization method and wet methods such as emulsion polymerization coagulation method, dispersion polymerization method, suspension polymerization method and dissolution suspension method. The wet method is preferred because it is easy to obtain a toner with excellent printing characteristics such as image reproducibility. Among the wet methods, since it is easy to obtain a toner with a small particle size distribution of micrometer order, polymerization methods such as emulsion polymerization coagulation method, dispersion polymerization method and suspension polymerization method are preferred. Among them, suspension polymerization method is more preferred.

[0044] The emulsion polymerization coagulation method is a method in which emulsified polymerizable monomers are polymerized to obtain resin particles, and the resin particles are coagulated with a colorant, etc. to produce colored resin particles. In addition, the dissolution suspension method is a method in which a solution in which a toner component such as a binder resin and a colorant is dissolved or dispersed in an organic solvent is added dropwise to an aqueous medium to form droplets, and then the organic solvent is removed to produce colored resin particles. The above methods can use known methods.

[0045] The colored resin particles constituting the toner of the first aspect of the present invention can be produced by any of a wet method and a dry method. When the colored resin particles are produced by the (A) suspension polymerization method, which is particularly preferred among wet methods, or by the (B) pulverization method, which is a representative method among dry methods, the following steps are performed. First, the (A) suspension polymerization method is described.

[0046] (A) Suspension polymerization

[0047] (A-1) Preparation step of polymerizable monomer composition

[0048] In the suspension polymerization method, first, a polymerizable monomer, a colorant, a charge control agent, a release agent, an additive having a polydiene structure, and other additives that may be used as needed are mixed and dissolved to prepare a polymerizable monomer composition. Mixing during the preparation of the polymerizable monomer composition can be performed using, for example, a medium-type disperser.

[0049] In the present invention, a polymerizable monomer refers to a compound that can be polymerized, and a binder resin is formed by polymerization of the polymerizable monomer. As a polymerizable monomer, a monovinyl monomer is preferably used as the main component constituting the polymerizable monomer. As a monovinyl monomer, for example, styrene monomers such as styrene, vinyl toluene, α-methylstyrene, and ethylstyrene; (meth) acrylate monomers such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, dimethylaminoethyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, and dimethylaminoethyl methacrylate; acrylic acid and methacrylic acid; nitrile compounds such as acrylonitrile and methacrylonitrile; amide compounds such as acrylamide and methacrylamide; olefins such as ethylene, propylene, and butene. These monovinyl monomers can be used alone or in combination of two or more. Among them, styrene monomers and (meth) acrylate monomers are preferred, and styrene and butyl acrylate are more preferred. Furthermore, from the viewpoint of further improving the low-temperature fixing property of the obtained toner, it is preferred to use at least a styrene-based monomer and a (meth)acrylate-based monomer as the monovinyl monomer.

[0050] In the binder resin used in the present invention, the content ratio of the styrene monomer unit is preferably 60% by mass or more, more preferably 65% ​​by mass or more, further preferably 68% by mass or more, particularly preferably 70% by mass or more, and the upper limit is preferably 85% by mass or less, more preferably 80% by mass or less, further preferably 77% by mass or less, and particularly preferably 74% by mass or less. In addition, the content ratio of the (methyl) acrylate monomer unit is preferably 20% by mass or more, more preferably 21% by mass or more, further preferably 21.5% by mass or more, further preferably 22% by mass or more, particularly preferably 24% by mass or more, and the upper limit is preferably 40% by mass or less, more preferably 35% by mass or less, further preferably 32% by mass or less, further preferably 30% by mass or less, particularly preferably 28% by mass or less, and most preferably 26% by mass or less. By making the content ratio of the styrene monomer unit and the (methyl) acrylate monomer unit in the above range, the storage stability of the obtained toner can be excellent, and the low temperature fixability can be further improved.

[0051] In the present invention, in order to improve hot offset and storage properties, it is preferred to use a monovinyl monomer and an arbitrary cross-linking polymerizable monomer at the same time. A cross-linking polymerizable monomer refers to a monomer having two or more polymerizable functional groups. As cross-linking polymerizable monomers, for example, aromatic divinyl compounds such as divinylbenzene, divinylnaphthalene and their derivatives; ester compounds in which alcohols having two or more hydroxyl groups and two or more carboxylic acids are ester-bonded, such as ethylene glycol dimethacrylate and diethylene glycol dimethacrylate; other divinyl compounds such as N,N-divinylaniline and divinyl ether; compounds having three or more vinyl groups, etc. These cross-linking polymerizable monomers can be used alone or in combination of two or more. The amount of the cross-linkable polymerizable monomer used is preferably 0.1 to 5 parts by mass, more preferably 0.15 to 2 parts by mass, and further preferably 0.2 to 0.7 parts by mass relative to 100 parts by mass of the monovinyl monomer, and the content of the cross-linkable polymerizable monomer unit in the binder resin used in the present invention is preferably 0.1 to 5% by mass, more preferably 0.15 to 2% by mass, and further preferably 0.2 to 0.7% by mass. By making the amount and content of the cross-linkable polymerizable monomer within the above range, the storage stability and low-temperature fixability of the obtained toner can be further improved.

[0052] In addition, when a macromonomer is used as a part of the polymerizable monomer, the preservation property and low-temperature fixability of the obtained toner can be further improved, so it is preferred to use any macromonomer. A macromonomer refers to a reactive oligomer or polymer having a carbon-carbon unsaturated bond that can be polymerized at the end of the molecular chain and a number average molecular weight (Mn) of usually 1000 to 30000. The macromonomer preferably can form a polymer having a Tg (glass transition temperature) higher than the Tg (glass transition temperature) of the polymer obtained without the macromonomer being polymerized. The amount of the macromonomer used is preferably 0.03 to 5 parts by mass, more preferably 0.05 to 1 part by mass, relative to 100 parts by mass of the monovinyl monomer.

[0053] In the present invention, a colorant is used. When a color toner (generally, four toners, black toner, cyan toner, yellow toner, and magenta toner are used) is produced, a black colorant, a cyan colorant, a yellow colorant, and a magenta colorant can be used respectively.

[0054] As the black colorant, for example, a pigment and / or dye such as carbon black, titanium black, and magnetic powder such as iron zinc oxide and iron nickel oxide can be used.

[0055] As the cyan colorant, for example, copper phthalocyanine pigments, derivatives thereof, and compounds such as anthraquinone pigments and / or dyes can be used. Specifically, CI Pigment Blue 2, 3, 6, 15, 15:1, 15:2, 15:3, 15:4, 16, 17:1, 60 and the like can be mentioned.

[0056] As yellow colorants, for example, azo pigments such as monoazo pigments and disazo pigments, condensed polycyclic pigments and / or dyes, and other compounds are used. Specifically, CI Pigment Yellow 3, 12, 13, 14, 15, 17, 62, 65, 73, 74, 83, 93, 97, 120, 138, 151, 155, 180, 181, 185, 186, 214, 219, CI Solvent Yellow 98, 162, etc. are mentioned.

[0057] As the magenta colorant, for example, azo pigments such as monoazo pigments and disazo pigments, condensed polycyclic pigments and / or dyes and other compounds can be used. Specifically, CI Pigment Red 31, 48, 57:1, 58, 60, 63, 64, 68, 81, 83, 87, 88, 89, 90, 112, 114, 122, 123, 144, 146, 149, 150, 163, 170, 184, 185, 187, 202, 206, 207, 209, 251, CI Solvent Violet 31, 47, 59, and CI Pigment Violet 19 can be mentioned.

[0058] In the present invention, each colorant may be used alone or in combination of two or more. The amount of the colorant used is preferably 1 to 10 parts by mass based on 100 parts by mass of the binder resin (100 parts by mass of the polymerizable monomer for obtaining the binder resin).

[0059] The charge control agent is not particularly limited as long as it is a charge control agent commonly used as a charge control agent for colorants. Among the charge control agents, positively or negatively charged charge control resins are preferred from the viewpoint of high compatibility with polymerizable monomers, ability to impart stable charge (charge stability) to colorant particles, and thereby ability to improve the dispersibility of the colorant. Furthermore, from the viewpoint of obtaining a negatively charged colorant, it is more preferred to use a negatively charged charge control resin.

[0060] Examples of the positively chargeable charge control agent include nigrosine dyes, quaternary ammonium salts, triaminotriphenylmethane compounds and imidazole compounds, polyamine resins preferably used as charge control resins, quaternary ammonium group-containing copolymers and quaternary ammonium salt group-containing copolymers.

[0061] As negatively charged charge control agents, there are: azo dyes containing metals such as Cr, Co, Al and Fe; salicylic acid metal compounds and alkyl salicylic acid metal compounds; and sulfonic acid group-containing copolymers, sulfonate group-containing copolymers, carboxylic acid group-containing copolymers and carboxylate group-containing copolymers, which are preferably used as charge control resins.

[0062] The weight average molecular weight (Mw) of the charge control resin is in the range of 5,000 to 30,000, preferably 8,000 to 25,000, and more preferably 10,000 to 20,000, as measured by gel permeation chromatography (GPC) using tetrahydrofuran in terms of polystyrene.

[0063] The copolymerization ratio of the monomer having a functional group such as a quaternary ammonium group or a sulfonate group in the charge control resin is preferably in the range of 0.5 to 12 mass %, more preferably in the range of 1.0 to 6 mass %, and further preferably in the range of 1.5 to 3 mass %.

[0064] The content of the charge control agent is preferably 0.01 to 10 parts by mass, more preferably 0.03 to 8 parts by mass, relative to 100 parts by mass of the binder resin (100 parts by mass of the polymerizable monomer used to obtain the binder resin). By making the addition amount of the charge control agent within the above range, the generation of fog and printing contamination can be effectively suppressed, and the dispersibility of the colorant can be appropriately improved.

[0065] As the release agent, any release agent generally used as a release agent for toner can be used without particular limitation, but from the viewpoint of appropriately improving the low-temperature fixability of the obtained toner, a release agent having a number average molecular weight (Mn) of 500 to 1500 is preferred, and a fatty acid ester compound having a number average molecular weight (Mn) of 500 to 1500 is preferred. In addition, the "fatty acid ester compound" refers to a product obtained by reacting a monohydric alcohol and / or a polyhydric alcohol with an ester of a saturated fatty acid and / or an unsaturated fatty acid.

[0066] Specific examples of monohydric alcohols include: monohydric saturated aliphatic alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 1-pentanol, 1-hexanol, octanol, 2-ethyl-1-hexanol, nonanol, lauryl alcohol, cetyl alcohol, stearyl alcohol, behenyl alcohol, etc.; monohydric unsaturated aliphatic alcohols such as allyl alcohol, methallyl alcohol, crotyl alcohol, oleyl alcohol, etc.; monohydric alicyclic alcohols such as cyclohexanol; monohydric aromatic alcohols such as phenol, benzyl alcohol (benzyl alcohol), methylphenol (cresol), p-ethylphenol, dimethylphenol (xylenol), nonylphenol, dodecylphenol, phenylphenol, naphthol, etc., etc.

[0067] Specific examples of the polyol include divalent saturated aliphatic alcohols such as ethylene glycol and propylene glycol; divalent aromatic alcohols such as catechol and hydroquinone; and trivalent or higher valent saturated aliphatic alcohols such as glycerol, pentaerythritol, dipentaerythritol and polyglycerol.

[0068] Among these monohydric alcohols and polyhydric alcohols, mono- to tetrahydric saturated aliphatic alcohols are preferred, stearyl alcohol, behenyl alcohol and pentaerythritol are more preferred, stearyl alcohol and behenyl alcohol are more preferred, and behenyl alcohol is particularly preferred.

[0069] The fatty acid as a raw material of the fatty acid ester compound is preferably a saturated fatty acid and / or unsaturated fatty acid having 12 to 22 carbon atoms, more preferably 14 to 18 carbon atoms. Among them, saturated fatty acids having the above carbon number are particularly preferred because fatty acid ester compounds having a number average molecular weight (Mn) of 500 to 1500 are easily obtained.

[0070] Specific examples of the saturated fatty acid having the above carbon number are not particularly limited, and include lauric acid (carbon number 12), myristic acid (carbon number 14), pentadecanoic acid (carbon number 15), palmitic acid (carbon number 16), heptadecanoic acid (carbon number 17), stearic acid (carbon number 18), arachidic acid (carbon number 20), and behenic acid (carbon number 22). Among these saturated fatty acids, stearic acid (carbon number 18), arachidic acid (carbon number 20), and behenic acid (carbon number 22) are preferred, and stearic acid (carbon number 18) is more preferred.

[0071] Specific examples of the unsaturated fatty acid are not particularly limited, but the following compounds can be mentioned.

[0072] Palmitoleic acid (CH 3 (CH 2 ) 5 CH=CH(CH 2 ) 7 COOH)

[0073] Oleic acid (CH 3 (CH 2 ) 7 CH=CH(CH 2 ) 7 COOH)

[0074] V-oleic acid (CH 3 (CH 2 ) 5 CH=CH(CH 2 ) 9 COOH)

[0075] Linoleic acid (CH 3 (CH 2 ) 3 (CH 2 CH=CH) 2 (CH 2 ) 7 COOH)

[0076] (9,12,15)-linolenic acid (CH 3 (CH 2 CH=CH) 3 (CH 2 ) 7 COOH)

[0077] (6,9,12)-linolenic acid (CH 3 (CH 2 ) 3 (CH 2 CH=CH) 3 (CH 2 ) 4 COOH)

[0078] Eleurotic acid (CH 3 (CH 2 ) 3 (CH=CH) 3 (CH 2 ) 7 COOH)

[0079] Arachidonic acid (CH 3 (CH 2 )3 (CH 2 CH=CH) 4 (CH 2 ) 3 COOH)

[0080] In addition, the above-mentioned saturated fatty acid and / or unsaturated fatty acid can be used alone or in combination of two or more. Among the saturated fatty acids and unsaturated fatty acids, saturated fatty acids are preferred, stearic acid, arachidic acid and behenic acid are more preferred, stearic acid and behenic acid are further preferred, and behenic acid is particularly preferred.

[0081] Such fatty acid ester compounds can be manufactured according to a conventional method. As the manufacture method of such fatty acid ester compounds, for example, a method for using the ester reaction of monohydric alcohol and / or polyhydric alcohol and saturated fatty acid and / or unsaturated fatty acid can be enumerated. In addition, as fatty acid ester compounds, commercially available fatty acid ester compounds can also be used, and as commercially available fatty acid ester compounds, for example, " WEP2 ", " WEP3 ", " WEP4 ", " WEP5 ", " WE6 ", " WE11 " (more than trade names) etc. made by NOF Corporation can be enumerated.

[0082] In addition, in the present invention, as a release agent, a release agent other than the fatty acid ester compound can be used in place of the above-mentioned fatty acid ester compound or together with the fatty acid ester compound, for example: low molecular weight polyolefin wax, its modified wax; plant-based natural wax such as jojoba oil; petroleum wax such as paraffin; mineral wax such as ozokerite; synthetic wax such as Fisher-Tropsch wax; polyol ester such as dipentaerythritol ester, etc. These can be used alone or in combination of two or more.

[0083] The number average molecular weight (Mn) of the release agent is preferably 500 to 1500, more preferably 550 to 1200, and further preferably 550 to 1100. The number average molecular weight (Mn) of the release agent can be measured based on, for example, a polystyrene conversion value measured by gel permeation chromatography (GPC) using tetrahydrofuran.

[0084] The content of the release agent is preferably 1 to 30 parts by mass, more preferably 8 to 28 parts by mass, and further preferably 12 to 25 parts by mass relative to 100 parts by mass of the binder resin (100 parts by mass of the polymerizable monomer used to obtain the binder resin). By making the content of the release agent within the above range, the particle size distribution of the obtained toner can be made relatively uniform, and the low-temperature fixing property can be further improved.

[0085] In addition, in the present invention, the colored resin particles further contain an additive having a polydiene structure having a solubility of 3 to 40 g / 100 g or more in styrene at a temperature of 40°C. In the present invention, by using such an additive having a polydiene structure, the compatibility of the additive having a polydiene structure with the release agent can be utilized to make the release agent finely dispersed in the colored resin particles in a state having a specific crystal domain structure. Moreover, in the present invention, by finely dispersing the release agent in a state having a specific crystal domain structure, the adhesion of the obtained toner can be effectively suppressed, and the effect of improving the low-temperature fixability brought about by the addition of the release agent can be fully exerted, and as a result, the storage stability and low-temperature fixability of the obtained toner can be excellent.

[0086] The additive having a polydiene structure used in the present invention is not particularly limited as long as it is a compound having a polydiene structure (i.e., a structure derived from a diene compound) and having a solubility of 3 to 40 g / 100 g in styrene at a temperature of 40°C. The solubility of the additive having a polydiene structure in styrene at a temperature of 40°C is preferably 5 to 30 g / 100 g, and more preferably 10 to 25 g / 100 g. When the solubility in styrene at a temperature of 40°C is too low, the dispersibility in the colored resin particles is reduced, thereby reducing the compatibility with the release agent and making the dispersion of the release agent insufficient. Moreover, as a result, the low-temperature fixing property and storage stability of the obtained toner are reduced. On the other hand, when the solubility in styrene is too high, the binder resin in the colored resin particles is miscible with the release agent and cannot form a crystal domain, and the low-temperature fixing property and storage stability of the toner are deteriorated.

[0087] The additive having a polydiene structure used in the present invention is not particularly limited, and examples thereof include: a conjugated diene-aromatic vinyl-based thermoplastic elastomer which is a polymer having a structural unit derived from a conjugated diene compound and a structural unit derived from an aromatic vinyl compound; a conjugated diene-based elastomer such as polybutadiene rubber and polyisoprene rubber, etc., preferably a conjugated diene-aromatic vinyl-based thermoplastic elastomer, and among the conjugated diene-aromatic vinyl-based thermoplastic elastomers, particularly preferably an unhydrogenated conjugated diene-aromatic vinyl-based thermoplastic elastomer.

[0088] The conjugated diene-aromatic vinyl thermoplastic elastomer having a polydiene structure as an additive used in the present invention has an unsaturated bond capable of polymerization reaction in its structure. By having such an unsaturated bond capable of polymerization reaction, the unsaturated bond capable of polymerization reaction reacts with the binding resin, thereby the conjugated diene-aromatic vinyl thermoplastic elastomer interacts with the release agent in a state fixed to the binding resin. Moreover, in the binding resin constituting the colored resin particles, the release agent can be well microdispersed, as a result, the adhesion of the obtained toner can be effectively suppressed, and the effect of improving the low-temperature fixability brought by adding the release agent can be fully exerted, as a result, the storage stability and low-temperature fixability of the obtained toner can be made more excellent. In addition, in the present invention, "unsaturated bond capable of polymerization reaction" means an unsaturated bond with polymerization activity, and preferably an olefinic carbon-carbon double bond with polymerization activity can be cited.

[0089] Examples of the conjugated diene-aromatic vinyl-based thermoplastic elastomer used in the present invention include random, block, graft or other copolymers of a conjugated diene monomer, an aromatic vinyl monomer and other monomers copolymerizable therewith as required, and hydrogenated products of such copolymers.

[0090] Such a conjugated diene-aromatic vinyl-based thermoplastic elastomer is not particularly limited, but a block copolymer including at least one aromatic vinyl polymer block and at least one conjugated diene polymer block can be preferably used from the viewpoint of further improving the storage stability and low-temperature fixing property of the toner.

[0091] Hereinafter, a block copolymer (hereinafter sometimes simply referred to as "block copolymer") comprising at least one aromatic vinyl polymer block and at least one conjugated diene polymer block as a representative example of a conjugated diene-aromatic vinyl-based thermoplastic elastomer is described. The block copolymer used in the present invention comprises at least one aromatic vinyl polymer block obtained by polymerizing an aromatic vinyl monomer and a conjugated diene polymer block obtained by polymerizing a conjugated diene monomer.

[0092] Aromatic vinyl monomers are not particularly limited as long as they are aromatic vinyl compounds, and include styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2,4-diisopropylstyrene, 2,4-dimethylstyrene, 4-tert-butylstyrene, 5-tert-butyl-2-methylstyrene, 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, 4-bromostyrene, 2-methyl-4,6-dichlorostyrene, 2,4-dibromostyrene, vinylnaphthalene, etc. Among them, styrene is preferably used. These aromatic vinyl monomers can be used alone or in combination of two or more in each aromatic vinyl polymer block. In addition, when the block copolymer has a plurality of aromatic vinyl polymer blocks, each aromatic vinyl polymer block can be composed of the same aromatic vinyl monomer unit or different aromatic vinyl monomer units.

[0093] As long as the aromatic vinyl polymer block has the aromatic vinyl monomer unit as the main repeating unit, it may also contain monomer units other than the aromatic vinyl monomer unit. As other monomers that can be used in the aromatic vinyl polymer block, there can be cited: conjugated diene monomers such as 1,3-butadiene and isoprene (2-methyl-1,3-butadiene); α,β-unsaturated nitrile monomers; unsaturated carboxylic acid or anhydride monomers; unsaturated carboxylic acid ester monomers; non-conjugated diene monomers, etc. The content of monomer units other than the aromatic vinyl monomer unit in the aromatic vinyl polymer block is preferably 20% by mass or less, more preferably 10% by mass or less, and particularly preferably substantially 0% by mass.

[0094] The conjugated diene monomer is not particularly limited as long as it is a conjugated diene compound, and 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, etc. can be cited. Among them, from the viewpoint of high effect of improving storage stability and low-temperature fixability, 1,3-butadiene and / or isoprene are preferably used, and isoprene is particularly preferably used. These conjugated diene monomers can be used alone or in combination of two or more in each conjugated diene polymer block. In addition, in the case where the block copolymer has a plurality of conjugated diene polymer blocks, each conjugated diene polymer block can be composed of the same conjugated diene monomer unit, or it can be composed of different conjugated diene monomer units. Furthermore, a part of the unsaturated bonds of each conjugated diene polymer block can also be hydrogenated.

[0095] As long as the conjugated diene polymer block has the conjugated diene monomer unit as the main repeating unit, it may also contain monomer units other than the conjugated diene monomer unit. As other monomers that can be used in the conjugated diene polymer block, there can be cited: aromatic vinyl monomers such as styrene and α-methylstyrene; α, β-unsaturated nitrile monomers; unsaturated carboxylic acid monomers; unsaturated carboxylic acid anhydride monomers; unsaturated carboxylic acid ester monomers; non-conjugated diene monomers, etc. The content of monomer units other than the conjugated diene monomer unit in the conjugated diene polymer block is preferably 20% by mass or less, more preferably 10% by mass or less, and particularly preferably substantially 0% by mass.

[0096] The vinyl bond content of the conjugated diene polymer block (the ratio of 1,2-vinyl bond units and 3,4-vinyl bond units to all conjugated diene monomer units in the conjugated diene polymer block) is not particularly limited, but is preferably 1 to 20 mol %, more preferably 2 to 15 mol %, and particularly preferably 3 to 10 mol %.

[0097] As long as the block copolymer comprises at least one aromatic vinyl polymer block and a conjugated diene polymer block respectively, the number of each polymer block and their bonding mode are not particularly limited. As a specific example of the block copolymer used in the present invention, the following examples can be cited. In the following specific example, Ar represents an aromatic vinyl polymer block, D represents a conjugated diene polymer block, X represents a residue of a coupling agent, and n represents an integer greater than 2.

[0098] (a) Aromatic vinyl-conjugated diene block copolymer represented by Ar-D

[0099] (b) Aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented by Ar-D-Ar and / or (Ar-D)nX

[0100] (c) Conjugated diene-aromatic vinyl-conjugated diene block copolymer represented by D-Ar-D and / or (D-Ar)nX

[0101] (d) an aromatic vinyl-conjugated diene-aromatic vinyl-conjugated diene block copolymer represented by Ar-D-Ar-D,

[0102] (e) A block copolymer composition formed by combining any two or more of the above (a) to (d)

[0103] In the present invention, as a block copolymer, it is preferred to use a block copolymer of an aromatic vinyl-conjugated diene block copolymer containing at least the above-mentioned (a) represented as Ar-D, and more preferably use a block copolymer of an aromatic vinyl-conjugated diene block copolymer containing at least the above-mentioned (a) represented as Ar-D and (b) represented as Ar-D-Ar and / or (Ar-D) nX. The content of the aromatic vinyl-conjugated diene block copolymer (that is, a diblock copolymer formed by a block of an aromatic vinyl polymer block and a polymer copolymerizable with an aromatic vinyl polymer) represented by Ar-D in the conjugated diene-aromatic vinyl-based thermoplastic elastomer used in the present invention is preferably 40 mass % (weight %) or more, preferably 50 mass % or more, more preferably 55 mass % or more. In addition, its upper limit is not particularly limited, preferably 98 mass % or less, more preferably 95 mass % or less. By making the content of the aromatic vinyl-conjugated diene block copolymer represented by Ar-D (i.e., a diblock copolymer formed by an aromatic vinyl polymer block and a block of a polymer copolymerizable with the aromatic vinyl polymer) in the conjugated diene-aromatic vinyl-based thermoplastic elastomer used in the present invention be 40% by mass or more, the resulting colorant can have high charging properties, suppress the bleeding of the release agent, and effectively suppress the ejection under high temperature and high humidity conditions and the adhesion to the scraper.

[0104] The weight average molecular weight (Mw(Ar)) of the aromatic vinyl polymer block Ar in the aromatic vinyl-conjugated diene block copolymer represented by Ar-D is not particularly limited, and is preferably 10,000 to 50,000, and more preferably 15,000 to 30,000. The weight average molecular weight (Mw(D)) of the conjugated diene polymer block D is not particularly limited, and is preferably 50,000 to 200,000, and more preferably 60,000 to 150,000.

[0105] In addition, the weight average molecular weight (Mw(Ar)) of the aromatic vinyl polymer block Ar in the aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented by Ar-D-Ar and / or (Ar-D)nX is not particularly limited, and is preferably 20,000 to 70,000, and more preferably 25,000 to 50,000. The weight average molecular weight (Mw(D)) of the conjugated diene polymer block D in the aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented by Ar-D-Ar and / or (Ar-D)nX is not particularly limited, and is preferably 100,000 to 300,000, and more preferably 120,000 to 250,000.

[0106] In addition, the said weight average molecular weight is a polystyrene conversion value measured by gel permeation chromatography (GPC) using tetrahydrofuran.

[0107] The content ratio of the aromatic vinyl monomer units in the block copolymer used in the present invention relative to the total monomer units is preferably 10 to 30% by mass, more preferably 12 to 25% by mass, and further preferably 15 to 25% by mass. By making the content ratio of the aromatic vinyl monomer units within the above range, the affinity of the block copolymer to the release agent and the affinity of the block copolymer to the binder resin can be highly balanced, and the storage stability and low-temperature fixing property of the obtained toner can be made more excellent.

[0108] When all polymer components constituting a block copolymer consist only of aromatic vinyl monomer units and conjugated diene monomer units, the content of the aromatic vinyl monomer units in the block copolymer can be measured as follows: according to the method described in Rubber Chem. Technol., 45, 1295 (1972), the block copolymer is subjected to ozone decomposition and then reduced with lithium aluminum hydride, so that the conjugated diene monomer unit portion is decomposed and only the aromatic vinyl monomer unit portion is taken out, so the total aromatic vinyl monomer unit content can be easily measured.

[0109] In addition, the weight average molecular weight (Mw) of the aromatic vinyl monomer unit in the block copolymer is not particularly limited, and is preferably 10,000 to 50,000, and more preferably 20,000 to 40,000, in terms of polystyrene conversion value measured by gel permeation chromatography (GPC) using tetrahydrofuran. In addition, the weight average molecular weight (Mw) of the conjugated diene monomer unit in the block copolymer is not particularly limited, and is preferably 50,000 to 200,000, and more preferably 60,000 to 180,000.

[0110] The melt index (MI) of the block copolymer is not particularly limited, and is selected as a value measured in accordance with ASTM D-1238 (condition G, 200°C, 5 kg), for example, within the range of 1 to 1000 g / 10 minutes, preferably 5 to 30 g / 10 minutes.

[0111] The block copolymer used in the present invention can be produced by conventional methods. Examples of methods for producing such block copolymers include, for example, sequentially polymerizing an aromatic vinyl monomer and a conjugated diene monomer to form polymer blocks by an anionic living polymerization method, and then reacting a coupling agent to couple the monomers as needed.

[0112] In addition, when a block copolymer containing at least the above-mentioned (a) aromatic vinyl-conjugated diene block copolymer represented by Ar-D and (b) aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented by Ar-D-Ar and / or (Ar-D)nX is used as the block copolymer used in the present invention, the following method can be adopted.

[0113] That is, the following method can be cited: first, an aromatic vinyl monomer is polymerized by an anionic living polymerization method, and then a conjugated diene monomer is added for polymerization, thereby obtaining a diblock copolymer with an active end. Next, a coupling agent less than 1 molar equivalent is added to the active end of the diblock copolymer with an active end, so that a part of the diblock copolymer with an active end undergoes a coupling reaction to obtain an aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented as (Ar-D)nX, and then a polymerization terminator is added to inactivate the remaining diblock copolymer with an active end to obtain a diblock copolymer represented as Ar-D. In this case, by using a bifunctional coupling agent such as dichlorosilane, monomethyldichlorosilane, dichlorodimethylsilane, diphenyldimethoxysilane, diphenyldiethoxysilane, dichloroethane, dibromoethane, dichloromethane, dibromomethane as a coupling agent, an aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented by Ar-D-Ar (D includes a residue of the coupling agent) can be obtained.

[0114] In the present invention, the content ratio of (a) the aromatic vinyl-conjugated diene block copolymer represented by Ar-D and (b) the aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented by Ar-D-Ar and / or (Ar-D)nX is not particularly limited, and the content ratio of (a) the aromatic vinyl-conjugated diene block copolymer represented by Ar-D is preferably 10 to 90% by mass, more preferably 20 to 80% by mass. In addition, the content ratio of (b) the aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented by Ar-D-Ar and / or (Ar-D)nX is preferably 10 to 90% by mass, more preferably 20 to 80% by mass.

[0115] In addition, as a conjugated diene-aromatic vinyl-based thermoplastic elastomer, a random copolymer of an aromatic vinyl monomer and a conjugated diene monomer can also be used instead of the above-mentioned block copolymer. The random copolymer of an aromatic vinyl monomer and a conjugated diene monomer can be manufactured by, for example, living anionic polymerization using an organic alkali metal compound as a polymerization initiator. As an organic alkali metal compound, for example, an organic lithium compound, an organic sodium compound, an organic potassium compound, etc. can be cited, specifically, organic monolithium compounds such as n-butyl lithium, sec-butyl lithium, tert-butyl lithium, hexyl lithium, phenyl lithium, distyryl lithium, etc. can be cited; organic polylithium compounds such as dilithium methane, 1,4-dilithium butane, 1,4-dilithium-2-ethylcyclohexane, 1,3,5-trilithium benzene, 1,3,5-tri(lithium methyl) benzene; organic sodium compounds such as sodium naphthalene; organic potassium compounds such as potassium naphthalene, etc. Among these organic metal compounds, n-butyl lithium is preferably used.

[0116] The content ratio of the aromatic vinyl monomer units in the random copolymer of the aromatic vinyl monomer and the conjugated diene monomer used in the present invention relative to the total monomer units is preferably 50% by mass or less, more preferably 45% by mass or less, and further preferably 40% by mass or less. By making the content ratio of the aromatic vinyl monomer units within the above range, the affinity of the random copolymer to the release agent and the affinity of the random copolymer to the binder resin can be highly balanced, and the storage stability and low-temperature fixability of the obtained toner can be made more excellent.

[0117] Furthermore, in the present invention, as an additive having a polydiene structure, a conjugated diene elastomer such as polybutadiene rubber and polyisoprene rubber can also be preferably used. Conjugated diene elastomers such as polybutadiene rubber and polyisoprene rubber can be produced by, for example, living anionic polymerization using an organic alkali metal compound as a polymerization initiator. As the organic alkali metal compound, for example, the above-mentioned organic alkali metal compounds can be used.

[0118] The weight average molecular weight (Mw) of the additive having a polydiene structure used in the present invention is not particularly limited, but is preferably 60000 to 350000, more preferably 80000 to 250000, in terms of polystyrene conversion value measured by gel permeation chromatography (GPC) using tetrahydrofuran. By setting the weight average molecular weight (Mw) within the above range, the storage stability and low-temperature fixing property of the obtained toner can be further improved.

[0119] The content of the additive having a polydiene structure is preferably 1 to 10 parts by mass, more preferably 1.5 to 8 parts by mass, and even more preferably 2 to 5 parts by mass relative to 100 parts by mass of the binder resin (100 parts by mass of the polymerizable monomer used to obtain the binder resin). By making the content of the additive having a polydiene structure within the above range, the effect of its addition, that is, the effect of improving the storage stability and low-temperature fixing property of the obtained toner, can be further improved.

[0120] Furthermore, in the present invention, an acrylic resin may be used as another additive in order to further suppress bleeding of the release agent.

[0121] The acrylic resin is a copolymer (acrylic acid ester copolymer) containing at least one of acrylic acid ester and methacrylic acid ester and at least one of acrylic acid and methacrylic acid as main components. Acrylic acid is preferred as the acid monomer.

[0122] Examples of acrylic resins include copolymers of acrylate and acrylic acid, copolymers of acrylate and methacrylic acid, copolymers of methacrylate and acrylic acid, copolymers of methacrylate and methacrylic acid, copolymers of acrylate, methacrylate and acrylic acid, copolymers of acrylate, methacrylate and methacrylic acid, and copolymers of acrylate, methacrylate, acrylic acid and methacrylic acid. Among them, copolymers of acrylate, methacrylate and acrylic acid are preferably used.

[0123] The acid value of the acrylic resin is usually 0.5 to 7 mgKOH / g, preferably 1 to 6 mgKOH / g, and more preferably 1.5 to 4 mgKOH / g. By making the acid value of the acrylic resin within the above range, the desired colored resin particles can be well prepared, and the heat-resistant storage property, low-temperature fixing property, and printing durability in temperature and humidity environments from low-temperature and low-humidity environments to high-temperature and high-humidity environments can be improved.

[0124] The acid value of the acrylic resin is a value measured in accordance with JIS K 0070, which is a standard oil and fat analysis method established by the Japan Industrial Standards Institute (JICS).

[0125] The weight average molecular weight (Mw) of the acrylic resin is usually 6,000 to 50,000, preferably 8,000 to 25,000, and more preferably 10,000 to 20,000.

[0126] When the weight average molecular weight (Mw) of the acrylic resin is within the above range, heat-resistant storage stability, durability, and low-temperature fixing property can be improved.

[0127] The glass transition temperature Tg of the acrylic resin is usually 60 to 85° C., preferably 65 to 80° C., and more preferably 70 to 77° C. When the glass transition temperature is within the above range, heat-resistant storage property and low-temperature fixing property can be improved.

[0128] The glass transition temperature Tg of the acrylic resin can be determined according to, for example, ASTM D3418-82.

[0129] The ratio of the acrylic acid ester monomer unit, the methacrylic acid ester monomer unit, the acrylic acid monomer unit and the methacrylic acid monomer unit in the acrylic resin is not particularly limited as long as the above-mentioned acid value, weight average molecular weight Mw and glass transition temperature are satisfied.

[0130] The ratio of the above four monomer units can be adjusted by the mass ratio of the addition amount of acrylate, methacrylate, acrylic acid and methacrylic acid during the synthesis of the copolymer. As the mass ratio of the addition amount, it can be, for example, (acrylate and / or methacrylate): (acrylic acid and / or methacrylic acid) = (99 to 99.95): (0.05 to 1), preferably (acrylate and / or methacrylate): (acrylic acid and / or methacrylic acid) = (99.4 to 99.9): (0.1 to 0.6), and more preferably (acrylate and / or methacrylate): (acrylic acid and / or methacrylic acid) = (99.5 to 99.7): (0.3 to 0.5). In addition, within the range that does not impair the effect of the present invention, the acrylate and / or methacrylate in these polymerizable monomers can be replaced by other monomers such as styrene derivatives, nitrile compounds and amide compounds exemplified by the monovinyl monomer constituting the above-mentioned binder resin. The ratio thereof is 10% by mass or less, preferably 2% by mass or less, of the total amount of acrylate and / or methacrylate added, and is preferably not replaced.

[0131] Examples of the acrylic esters that can be used in the acrylic resin include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-pentyl acrylate, sec-pentyl acrylate, isopentyl acrylate, neopentyl acrylate, n-hexyl acrylate, isohexyl acrylate, neohexyl acrylate, sec-hexyl acrylate and tert-hexyl acrylate. Among them, ethyl acrylate, n-propyl acrylate, isopropyl acrylate and n-butyl acrylate are preferred, and n-butyl acrylate is more preferred.

[0132] Methacrylates that can be used in the acrylic resin include, for example, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, n-pentyl methacrylate, sec-pentyl methacrylate, isopentyl methacrylate, neopentyl methacrylate, n-hexyl methacrylate, isohexyl methacrylate, neohexyl methacrylate, sec-hexyl methacrylate, and tert-hexyl methacrylate. Among them, methyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, and n-butyl methacrylate are preferred, and methyl methacrylate is more preferred.

[0133] The amount of the acrylic resin added is preferably 0.3 to 4 parts by mass, more preferably 0.5 to 3.0 parts by mass, and further preferably 0.7 to 2.0 parts by mass relative to 100 parts by mass of the binder resin (100 parts by mass of the polymerizable monomer used to obtain the binder resin). By making the amount of the acrylic resin added within the above range, the environmental stability can be improved and the effect of its addition can be fully exerted.

[0134] The acrylic resin may be a commercially available acrylic resin or may be produced by a known method such as solution polymerization, aqueous solution polymerization, ion polymerization, high temperature and high pressure polymerization, or suspension polymerization.

[0135] Furthermore, as other additives, a molecular weight regulator can be used. As a molecular weight regulator, there is no particular limitation as long as it is a molecular weight regulator commonly used as a molecular weight regulator for toners, and examples thereof include: thiols such as tert-dodecyl mercaptan, n-dodecyl mercaptan, n-octyl mercaptan, and 2,2,4,6,6-pentamethylheptane-4-thiol; thiuram disulfides such as tetramethylthiuram disulfide, tetraethylthiuram disulfide, tetrabutylthiuram disulfide, N,N'-dimethyl-N,N'-diphenylthiuram disulfide, and N,N'-dioctadecyl-N,N'-diisopropylthiuram disulfide. These molecular weight regulators can be used alone or in combination of two or more. The amount of the molecular weight regulator used is preferably 0.01 to 10 parts by mass, and more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the binder resin (100 parts by mass of the polymerizable monomer used to obtain the binder resin).

[0136] (A-2) Suspension step of obtaining a suspension (droplet formation step)

[0137] Next, the polymerizable monomer composition obtained by the preparation process of the above-mentioned (A-1) polymerizable monomer composition, comprising a polymerizable monomer, a colorant, a charge control agent, a release agent, and an additive having a polydiene structure, is dispersed in an aqueous dispersion medium, and after adding a polymerization initiator, droplets of the polymerizable monomer composition are formed. Here, suspension means that droplets of the polymerizable monomer composition are formed in an aqueous dispersion medium. The dispersion treatment for droplet formation can be carried out using a device capable of strong stirring, such as an in-line emulsifying disperser (Pacific Machinery & Engineering Co., Ltd., trade name: Milder), a high-speed emulsifying / dispersing machine (PRIMIX Corporation, trade name: TKHOMOMIXER MARK II type), etc.

[0138] As polymerization initiators, persulfates such as potassium persulfate and ammonium persulfate can be cited; azo compounds such as 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide), 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile; organic peroxides such as di-tert-butyl peroxide, benzoyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-hexyl peroxy-2-ethylbutyrate, diisopropyl peroxydicarbonate, di-tert-butyl peroxyisobutyrate, and tert-butyl peroxyisobutyrate. They can be used alone or in combination of two or more. Among them, organic peroxides are preferably used from the viewpoint of being able to reduce residual polymerizable monomers and having excellent printing durability. Among organic peroxides, peroxyesters are preferred, and non-aromatic peroxyesters, that is, peroxyesters having no aromatic ring, are more preferred, from the viewpoint of good initiator efficiency and ability to reduce residual polymerizable monomers.

[0139] As described above, the polymerization initiator may be added after the polymerizable monomer composition is dispersed in the aqueous medium and before droplets are formed, or may be added to the polymerizable monomer composition before being dispersed in the aqueous medium (a medium containing water as a main component).

[0140] The amount of the polymerization initiator used for polymerization of the polymerizable monomer composition is preferably 0.1 to 20 parts by mass, more preferably 0.3 to 15 parts by mass, and particularly preferably 1 to 10 parts by mass relative to 100 parts by mass of the binder resin (100 parts by mass of the polymerizable monomer for obtaining the binder resin).

[0141] In the present invention, it is preferred that the aqueous medium contains a dispersion stabilizer. Examples of the dispersion stabilizer include sulfates such as barium sulfate and calcium sulfate; carbonates such as barium carbonate, calcium carbonate, and magnesium carbonate; phosphates such as calcium phosphate; metal oxides such as aluminum oxide and titanium oxide; inorganic compounds such as metal hydroxides such as aluminum hydroxide, magnesium hydroxide, and iron hydroxide; water-soluble polymers such as polyvinyl alcohol, methylcellulose, and gelatin; anionic surfactants; nonionic surfactants; organic compounds such as amphoteric surfactants. The above-mentioned dispersion stabilizers can be used alone or in combination of two or more. The amount of the dispersion stabilizer added is preferably 0.1 to 20 parts by mass, and more preferably 0.2 to 10 parts by mass, relative to 100 parts by mass of the binder resin (100 parts by mass of the polymerizable monomer used to obtain the binder resin).

[0142] Among the above-mentioned dispersion stabilizers, inorganic compounds, especially colloids of metal hydroxides that are sparingly soluble in water, are preferred. By using inorganic compounds, especially colloids of metal hydroxides that are sparingly soluble in water, the particle size distribution of the colored resin particles can be narrowed, and the amount of the dispersion stabilizer remaining after washing can be reduced, so that the environmental stability will not be deteriorated, and the obtained toner can reproduce images more clearly.

[0143] (A-3) Polymerization step

[0144] By heating the desired suspension (aqueous dispersion medium containing droplets of the polymerizable monomer composition) obtained in the above-mentioned step (A-2) of obtaining a suspension (droplet formation step) to initiate polymerization, an aqueous dispersion of colored resin particles containing a binder resin, a colorant, a charge control agent, a release agent, and an additive having a polydiene structure can be obtained.

[0145] The polymerization temperature of the present invention is preferably 50° C. or higher, and more preferably 60 to 95° C. The polymerization time of the present invention is preferably 1 to 20 hours, and more preferably 2 to 15 hours.

[0146] From the viewpoint of performing polymerization in a state where droplets of the polymerizable monomer composition are stably dispersed, the polymerization step may be performed while performing a dispersion treatment by stirring, following the step (A-2) of obtaining a suspension (droplet forming step).

[0147] In the present invention, the colored resin particles thus obtained may be directly added with an external additive and used as a toner, or may be colored resin particles of a so-called core-shell type (or also referred to as a "capsule type") type obtained by using the colored resin particles obtained by the polymerization process as a core layer and forming a shell layer different from the core layer on the outer side thereof. The core-shell type colored resin particles can be further improved in storage stability and low-temperature fixing property of the obtained toner by coating the core layer formed of a low-softening-point substance with a substance having a higher softening point than the core layer.

[0148] The method for producing the core-shell type colored resin particles is not particularly limited and can be produced by a conventionally known method. From the viewpoint of production efficiency, an in situ polymerization method or a phase separation method is preferred.

[0149] The following describes a method for producing core-shell type colored resin particles by an in-situ polymerization method.

[0150] In the in-situ polymerization method, a polymerizable monomer for forming a shell layer (shell polymerizable monomer) and a shell polymerization initiator are added to an aqueous dispersion medium in which colored resin particles are dispersed, and polymerization is performed to obtain core-shell type colored resin particles.

[0151] As the polymerizable monomer for the shell, the same polymerizable monomers as those described above can be used. Among them, monomers that can give a polymer having a Tg exceeding 80° C., such as styrene and methyl methacrylate, are preferably used alone or in combination of two or more.

[0152] Examples of the polymerization initiator for shell used in the polymerization of the polymerizable monomer for shell include metal persulfate salts such as potassium persulfate and ammonium persulfate, and water-soluble azo compounds such as 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide) and 2,2'-azobis-(2-methyl-N-(1,1-bis(hydroxymethyl)-2-hydroxyethyl)propionamide). The amount of the polymerization initiator for shell used is preferably 0.1 to 30 parts by mass, more preferably 1 to 20 parts by mass, relative to 100 parts by mass of the polymerizable monomer for shell.

[0153] The polymerization temperature of the shell layer is preferably 50° C. or higher, and more preferably 60 to 95° C. The polymerization time of the shell layer is preferably 1 to 20 hours, and more preferably 2 to 15 hours.

[0154] (A-4) Cleaning, filtration, dehydration and drying process

[0155] The aqueous dispersion of colored resin particles obtained in the polymerization step (A-3) is preferably subjected to a series of operations of washing, filtering, dehydrating and drying, which are repeated several times as necessary, according to a conventional method after completion of the polymerization.

[0156] First, in order to remove the dispersion stabilizer remaining in the aqueous dispersion of the colored resin particles, it is preferred to add an acid or an alkali to the aqueous dispersion of the colored resin particles for washing. When the dispersion stabilizer used is an inorganic compound soluble in acid, it is preferred to add an acid to the aqueous dispersion of the colored resin particles for washing. On the other hand, when the dispersion stabilizer used is an inorganic compound soluble in alkali, it is preferred to add an alkali to the aqueous dispersion of the colored resin particles for washing.

[0157] When an acid-soluble inorganic compound is used as a dispersion stabilizer, it is preferred to add an acid to the aqueous dispersion of the colored resin particles to adjust the pH to preferably 6.5 or less, more preferably 6 or less. As the acid to be added, inorganic acids such as sulfuric acid, hydrochloric acid, and nitric acid, and organic acids such as formic acid and acetic acid can be used, and sulfuric acid is particularly preferred because of its high removal efficiency of the dispersion stabilizer and low burden on production equipment.

[0158] The dehydration and filtration methods can use various known methods, etc., and are not particularly limited. For example, centrifugal filtration, vacuum filtration, pressure filtration, etc. can be mentioned. In addition, the drying method is also not particularly limited, and various methods can be used.

[0159] (B) Crushing method

[0160] When the colored resin particles are produced by a pulverization method, the production can be carried out through the following steps.

[0161] First, use a mixer such as a ball mill, a V-type mixer, FM Mixer (trade name), a high-speed mixing and dissolving machine, a Banbury mixer, Forberg, etc. to mix a bonding resin, a colorant, a charge control agent, a release agent, and an additive with a polydiene structure, and further other additives added as needed. Next, use a pressure kneader, a double-shaft extrusion mixer, a roller, etc. to heat the mixture obtained above and mix it. Use a pulverizer such as a hammer mill, a shredder, a roller mill, etc. to coarsely pulverize the obtained mixture. Then, after using a pulverizer such as a jet mill, a high-speed rotary pulverizer, etc. to perform fine pulverization, use a classifier such as a wind classifier, an airflow classifier, etc. to classify it into a desired particle size, so that colored resin particles can be obtained by a pulverization method.

[0162] In addition, the binder resin, colorant, charge control agent, release agent and additive having a polydiene structure used in the pulverization method, and other additives added as needed can be those listed in the above-mentioned (A) suspension polymerization method. In addition, the colored resin particles obtained by the pulverization method are the same as the colored resin particles obtained by the above-mentioned (A) suspension polymerization method, and can also be made into core-shell type colored resin particles by a method such as an in-situ polymerization method.

[0163] In addition, as the binder resin, in addition to the above-mentioned binder resins, resins that have been widely used in toners can also be used. Specific examples of the binder resin used in the pulverization method include polystyrene, styrene-butyl acrylate copolymer, polyester resin, and epoxy resin.

[0164] (Colored resin particles)

[0165] The colored resin particles can be obtained by the above-mentioned (A) suspension polymerization method or (B) pulverization method.

[0166] The colored resin particles constituting the toner are described below. The colored resin particles described below include both core-shell type colored resin particles and non-core-shell type colored resin particles.

[0167] In the colored resin particles used in the first aspect of the present invention, as the crystal domains of the release agent contained in the colored resin particles, a specific number of the above-mentioned crystal domains having a specific shape are included. That is, when the cross section of the colored resin particles is observed by a transmission electron microscope (TEM), in the 2μm×2μm square field of view of the cross section of the colored resin particles, the number of crystal domains of the release agent with an aspect ratio in the range of 2 to 10 is in the range of 2 to 30. In the first aspect of the present invention, the release agent contained in the colored resin particles is finely dispersed in a state having a crystal domain structure with an aspect ratio of 2 to 10, and the number of the above-mentioned crystal domains in the 2μm×2μm square field of view is in the range of 2 to 30, thereby effectively suppressing the adhesion of the obtained colorant and fully exerting the effect of improving the low-temperature fixability brought about by the addition of the release agent. Then, as a result, the storage stability and low-temperature fixability of the obtained colorant can be excellent.

[0168] In a 2 μm×2 μm square field of view, the number of crystal domains of the release agent with an aspect ratio in the range of 2 to 10 is 2 to 30, preferably 3 to 27, and more preferably 5 to 25. In addition, in the first aspect of the present invention, the number of crystal domains of the release agent with an aspect ratio in the range of 2 to 10 may be in the above range, and from the viewpoint of further improving the effect of the present invention, it is preferred that the number of crystal domains of the release agent with an aspect ratio in the range of 3 to 8 in a 2 μm×2 μm square field of view is also in the above range.

[0169] In the visual field of 2μm×2μm square, the number of crystal domains of the release agent with an aspect ratio in the range of 2 to 10 and the number of crystal domains of the release agent with an aspect ratio in the range of 3 to 8 can be measured by, for example, the following method. That is, first, after dispersing the colored resin particles in the epoxy resin, solidify it, cool it to a temperature of -80°C, and cut it by a microtome to make a thin slice. Then, the thin slice is stained with ruthenium tetroxide aqueous solution vapor, observed by a transmission electron microscope (TEM), and the number of crystal domains of the release agent and the aspect ratio of the crystal domains of the release agent in the visual field of 2μm×2μm square of the cross section of the colored resin particles are calculated by image analysis. Then, the number of crystal domains of the release agent with an aspect ratio in the range of 2 to 10 and the number of crystal domains of the release agent with an aspect ratio in the range of 3 to 8 can be obtained. In addition, during these measurements, observation can be performed in a viewing field that is wider than 2 μm × 2 μm square (for example, a viewing field in which cross sections of 5 or more colored resin particles can be observed), and the number of crystal domains of the release agent with an aspect ratio in the range of 2 to 10 and the number of crystal domains of the release agent with an aspect ratio in the range of 3 to 8 of the colored resin particles observed in the viewing field are calculated, and the number of crystal domains is converted to a viewing field of 2 μm × 2 μm square based on the obtained calculation results, and the result is used as the measured value.

[0170] In addition, as a method for making the number of crystal domains of the release agent with an aspect ratio in the range of 2 to 10 within the above range, there is no particular limitation, and a method of making the colored resin particles contain an additive having a polydiene structure. Specifically, by containing an additive having a polydiene structure, the release agent can be appropriately dispersed in the colored resin particles by utilizing the compatibility of the additive having a polydiene structure with the release agent, thereby making it possible to make the number of crystal domains of the release agent with an aspect ratio in the range of 2 to 10 within the above range. In addition, in the first aspect of the present invention, as a method for controlling the number of crystal domains of the release agent with an aspect ratio in the range of 2 to 10 within the above range, there is no particular limitation, and a method of adjusting the type of additive having a polydiene structure used, the type of release agent used, the amount of the additive having a polydiene structure used, and the amount of the release agent used, etc., can be cited, and these can also be combined.

[0171] In addition, the average value of the aspect ratio of the crystal domains of the release agent contained in the colored resin particles is not particularly limited, but is preferably 2 to 10, more preferably 3 to 9, and further preferably 3.5 to 8.5. In addition, the average major diameter (average value of the major diameter) of the crystal domains of the release agent is preferably 0.20 to 1.0 μm, more preferably 0.25 to 0.90 μm, and the average minor diameter (average value of the minor diameter) of the crystal domains of the release agent is preferably 0.03 to 0.15 μm, more preferably 0.04 to 0.10 μm. By making the average value of the aspect ratio, the average major diameter, and the average minor diameter of the crystal domains of the release agent within the above ranges, the effect of improving the storage stability and low-temperature fixing property can be further improved. In addition, the average value of the aspect ratio, the average major axis, and the average minor axis of the crystal domains of the release agent can be calculated by the following method: when measuring the number of crystal domains of the release agent with an aspect ratio in the range of 2 to 10 and the number of crystal domains of the release agent with an aspect ratio in the range of 3 to 8, the aspect ratio, the major axis, and the minor axis are measured for each crystal domain of the release agent that is the subject of measurement, and the average value of all the crystal domains of the release agent that are the subject of measurement is calculated.

[0172] From the viewpoint of image reproducibility, the volume average particle diameter Dv of the colored resin particles is preferably 3 to 15 μm, more preferably 4 to 12 μm, and further preferably 5 to 8 μm. When the volume average particle diameter Dv of the colored resin particles is smaller than the above range, the fluidity of the toner may be reduced, and the image quality may be easily deteriorated due to fogging, etc. On the other hand, when the volume average particle diameter Dv of the colored resin particles exceeds the above range, the resolution of the obtained image may be reduced.

[0173] In addition, from the viewpoint of image reproducibility, the particle size distribution (Dv / Dn) which is the ratio of the volume average particle size (Dv) to the number average particle size (Dn) of the colored resin particles is preferably 1.00 to 1.30, and more preferably 1.00 to 1.20. When the particle size distribution (Dv / Dn) of the colored resin particles exceeds the above range, the fluidity of the toner may be reduced, and the image quality may be easily deteriorated due to fogging, etc. In addition, the volume average particle size Dv and the number average particle size Dn of the colored resin particles can be measured using, for example, a particle size analyzer (manufactured by BECKMAN COULTER CO., Ltd., trade name: Multisizer) or the like.

[0174] Furthermore, from the viewpoint of image reproducibility, the average circularity of the colored resin particles is preferably from 0.960 to 1.000, more preferably from 0.970 to 1.000, and even more preferably from 0.980 to 1.000.

[0175] In addition, from the viewpoint of improving the hot offset property and the low-temperature fixing property, the gel content (amount of tetrahydrofuran insoluble components) of the above-mentioned colored resin particles is preferably 1 to 50% by weight, more preferably 5 to 47% by weight, further preferably 10 to 45% by weight, and particularly preferably 15 to 40% by weight.

[0176] The weight average molecular weight (Mw) of the colored resin particles is preferably 20,000 to 200,000, more preferably 30,000 to 180,000, further preferably 35,000 to 150,000, and particularly preferably 40,000 to 90,000.

[0177] The above-mentioned colored resin particles can be used as a colorant directly or can be mixed with carrier particles (ferrite, iron powder, etc.) to use as a colorant. In order to adjust the charging properties, fluidity, storage properties, etc. of the colorant, a high-speed mixer (for example, FM Mixer (trade name, manufactured by Nippon Coke & Engineering Co., Ltd.) etc.) can be used to add / mix external additives into the colored resin particles to prepare a single-component colorant. Furthermore, the colored resin particles and external additives can be mixed and further mixed with carrier particles to prepare a two-component colorant.

[0178] The agitator used for the external addition treatment is not particularly limited as long as it is a stirring device that can cause the external additive to adhere to the surface of the colored resin particles. For example, a stirrer capable of mixing and stirring, such as FM Mixer (trade name, manufactured by Nippon Coke & Engineering Co., Ltd.), Super Mixer (trade name, manufactured by Kawada Manufacturing Co., Ltd.), Q Mixer (trade name, manufactured by Nippon Coke & Engineering Co., Ltd.), Mechanofusion System (trade name, manufactured by Hosokawa Micron Corporation), and Mechanomill (trade name, manufactured by OKADA SEIKO. CO., LTD.), can be used for the external addition treatment.

[0179] As external additives, there can be mentioned: inorganic particles including silicon dioxide, titanium oxide, aluminum oxide, zinc oxide, tin oxide, calcium carbonate, calcium phosphate and cerium oxide; organic particles including polymethyl methacrylate resin, silicone resin and melamine resin, etc. Among them, inorganic particles are preferred, silicon dioxide and titanium oxide are more preferred, and silicon dioxide is particularly preferred. In addition, it is preferred to use two or more particles as external additives. In addition, these external additives can also be used separately, but it is preferred to use two or more in combination.

[0180] The external additive is preferably used in a ratio of 0.3 to 6 parts by mass, more preferably 1.2 to 3 parts by mass, based on 100 parts by mass of the colored resin particles.

[0181] In the toner according to the first aspect of the present invention, the following colored resin particles are used as the colored resin particles, the above-mentioned colored resin particles contain a binder resin, a colorant, a charge control agent, a release agent and an additive having a polydiene structure whose solubility in styrene at a temperature of 40°C is 3 to 40 g / 100 g, and in a 2μm×2μm square field of view of a cross section of the colored resin particles observed by a transmission electron microscope (TEM), the number of crystal domains of the release agent with an aspect ratio in the range of 2 to 10 is 2 to 30. According to such a toner according to the first aspect of the present invention, the storage stability and low-temperature fixing property are excellent, and therefore it can fully meet the recent requirements for reducing energy consumption and increasing printing speed.

[0182] <Toner for Electrostatic Image Development of Second Aspect>

[0183] Furthermore, the electrostatic image developing toner according to the second aspect of the present invention contains colored resin particles including a binder resin, a colorant, a charge control agent, a release agent, and an additive having a polydiene structure.

[0184] The solubility of the additive having a polydiene structure in styrene at a temperature of 40° C. is 3 to 40 g / 100 g.

[0185] The storage modulus G'(60) of the colored resin particles at 60°C obtained by dynamic viscoelasticity measurement is 1.6×10 8 ~5.0×10 8 Pa.

[0186] The colored resin particles constituting the toner of the second aspect of the present invention can be manufactured by any of dry methods such as a pulverization method or wet methods such as an emulsion polymerization coagulation method, a dispersion polymerization method, a suspension polymerization method, and a dissolution suspension method, as in the case of the toner of the first aspect described above. From the perspective of easily obtaining a toner having excellent printing characteristics such as image reproducibility, it is preferably manufactured by a wet method. In addition, as for the colored resin particles constituting the toner of the second aspect of the present invention, when the colored resin particles are manufactured by the (A) suspension polymerization method, which is particularly preferred among wet methods, or by the (B) pulverization method, which is a representative method among dry methods, the same steps as in the case of the toner of the first aspect described above can be used.

[0187] When the colored resin particles constituting the toner of the second aspect of the present invention are obtained by the (A) suspension polymerization method, the production can be carried out through (A-1) a step of preparing a polymerizable monomer composition, (A-2) a suspension step (droplet formation step) of obtaining a suspension, (A-3) a polymerization step, and (A-4) a washing, filtering, dehydration, and drying step, as in the case of the toner of the first aspect described above. At this time, as the raw materials for the production of the colored resin particles such as the polymerizable monomer, the colorant, the charge control agent, the release agent, the additive having a polydiene structure, and other additives used as needed, the same raw materials as in the case of the toner of the first aspect described above can be used, and the production conditions can also be the same.

[0188] In addition, when the colored resin particles constituting the colorant of the second aspect of the present invention are obtained by the (B) pulverization method, they can also be manufactured by the same method as the case of the colorant of the first aspect mentioned above, and as the raw materials for the manufacture of the colored resin particles, the same raw materials as the case of the colorant of the first aspect mentioned above can also be used, and the manufacturing conditions can also be the same.

[0189] The colored resin particles constituting the toner according to the second aspect of the present invention can be produced by, for example, the above-mentioned (A) suspension polymerization method or (B) pulverization method. In the second aspect of the present invention, the storage modulus G'(60) at 60°C obtained by dynamic viscoelasticity measurement is controlled to be 1.6×10 8 ~5.0×10 8 Colored resin particles having a storage modulus G'(60) at 60°C obtained by dynamic viscoelasticity measurement of the colored resin particles are used as colored resin particles. By controlling the storage modulus G'(60) at 60°C of the colored resin particles to be within the above range, the blocking of the obtained toner can be effectively suppressed, and the effect of improving the low-temperature fixability brought about by the addition of the release agent can be fully exerted. Moreover, as a result, the storage stability and low-temperature fixability of the obtained toner can be made excellent.

[0190] The storage modulus G'(60) of the colored resin particles at 60°C obtained by dynamic viscoelasticity measurement is within 1.6×10 8 ~5.0×10 8 Pa, preferably within the range of 1.8×10 8 ~4.5×10 8 The range of Pa is more preferably 2.0×10 8 ~4.0×10 8 The range of Pa.

[0191] In the second aspect of the present invention, the storage modulus G'(60) of the colored resin particles at 60°C obtained by the dynamic viscoelasticity measurement may be within the above range. From the viewpoint of achieving better storage stability and low-temperature fixing property of the obtained toner, the storage modulus G'(100) of the colored resin particles at 100°C obtained by the dynamic viscoelasticity measurement is preferably controlled within 1.0×10 5 ~3.0×10 5 The range of Pa is preferably controlled within 1.1×10 5 ~2.9×10 5 The range of Pa is preferably controlled within 1.2×10 5 ~2.8×10 5 The range of Pa.

[0192] The ratio G'(60) / G'(100) of the storage modulus G'(60) of the colored resin particles at 60°C and the storage modulus G'(100) at 100°C obtained by dynamic viscoelasticity measurement is not particularly limited, but is preferably controlled within 1.0×10 3 ~5.0×10 3 The range is preferably controlled within 1.0×10 3 ~4.0×10 3 The range is preferably controlled within 1.0×10 3 ~3.0×10 3 range.

[0193] The storage modulus G'(60) at 60°C and the storage modulus G'(100) at 100°C of the colored resin particles are not particularly limited, but can be determined by the following method: The colored resin particles are sandwiched between a pair of plates with a load of 20 g (when the colored resin particles are A sample in which the colored resin particles are uniformly arranged over an area and are sandwiched by a pair of plates with a load of 20 g is used as a measurement sample, and the dynamic viscoelasticity measurement is performed in the range of 45 to 150°C under the conditions of a measurement frequency of 24 Hz and a heating rate of 5°C / min using a dynamic viscoelasticity measuring device of a rotational plane rheometer.

[0194] In addition, in the second aspect of the present invention, as a method for making the storage modulus G'(60) of the colored resin particles at 60°C and the storage modulus G'(100) of the colored resin particles at 100°C within the above range, there is no particular limitation, and a method of making the colored resin particles contain an additive having a polydiene structure. Specifically, by containing an additive having a polydiene structure, the compatibility of the additive having a polydiene structure with the release agent can be utilized to appropriately disperse the release agent in the colored resin particles, thereby making it possible to make the storage modulus G'(60) of the colored resin particles at 60°C and the storage modulus G'(100) of the colored resin particles at 100°C within the above range. In addition, in the first aspect of the present invention, as a method for further controlling the storage modulus G'(60) of the colored resin particles at 60°C to 1.6×10 8 ~5.0×10 8 Pa is not particularly limited, and examples thereof include adjusting the type of additive having a polydiene structure, the type of release agent, the amount of additive having a polydiene structure, and the amount of release agent, and these methods may be combined. Similarly, as a method for further controlling the storage modulus G'(100) of the colored resin particles at 100°C to 1.0×10 5 ~3.0×10 5 The method for adjusting Pa within the range is not particularly limited, and examples thereof include adjusting the type of the additive having a polydiene structure, the type of the release agent, the amount of the additive having a polydiene structure, and the amount of the release agent, and these may be combined.

[0195] The volume average particle size (Dv), number average particle size (Dn), particle size distribution (Dv / Dn), and average circularity of the colored resin particles are preferably in the same ranges for the same reasons as those of the colored resin particles of the first aspect described above.

[0196] The gel content (amount of tetrahydrofuran insoluble components) and weight average molecular weight (Mw) of the colored resin particles are preferably in the same ranges for the same reasons as those of the colored resin particles according to the first aspect.

[0197] The above-mentioned colored resin particles can be used directly as a toner or mixed with carrier particles (ferrite, iron powder, etc.) to use as a toner. In order to adjust the charging property, fluidity, storage property, etc. of the toner, a high-speed mixer (for example, FM Mixer (trade name, manufactured by Nippon Coke & Engineering Co., Ltd.) etc.) can be used to add / mix external additives to the colored resin particles to form a single-component toner. Furthermore, the colored resin particles and the external additives and the carrier particles can be mixed to form a two-component toner. As a mixer for external addition treatment, the same mixer as in the first aspect can be used. In addition, as an external additive, the same external additive as in the first aspect can be used in the same proportion.

[0198] The toner according to the second aspect of the present invention uses the following colored resin particles as colored resin particles, wherein the colored resin particles contain a binder resin, a colorant, a charge control agent, a release agent, and an additive having a polydiene structure whose solubility in styrene at a temperature of 40° C. is 3 to 40 g / 100 g, and the storage modulus G'(60) of the colored resin particles at 60° C. determined by dynamic viscoelasticity measurement is controlled within 1.6×10 8 ~5.0×10 8 With such a range of Pa, the toner according to the second aspect of the present invention has excellent storage stability and low-temperature fixing property, and can therefore fully meet recent demands for reduction in energy consumption and increase in printing speed.

[0199] Example

[0200] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. In addition, "parts" and "%" are based on mass unless otherwise specified.

[0201] The test methods performed in the present examples and comparative examples are as follows.

[0202] (1) Weight average molecular weight of conjugated diene-aromatic vinyl based thermoplastic elastomer

[0203] The molecular weight was determined as polystyrene conversion by high performance liquid chromatography with tetrahydrofuran as carrier at a flow rate of 0.35 ml / min. The apparatus used was HLC8220 manufactured by Tosoh Corporation, the column used was Shodex (registered trademark) KF-404HQ manufactured by ShowaDenko Group connected in three columns (column temperature 40°C), the detector used was a differential refractometer and an ultraviolet detector, and the molecular weight was calibrated at 12 points of standard polystyrene (from 500 to 3 million) manufactured by Polymer Laboratories Ltd.

[0204] (2) Content of each block copolymer in the conjugated diene-aromatic vinyl-based thermoplastic elastomer

[0205] It was determined from the area ratio of the peaks corresponding to the respective block copolymers in the graph obtained by the high performance liquid chromatography.

[0206] (3) Weight average molecular weight of the styrene polymer block constituting the block copolymer of the conjugated diene-aromatic vinyl-based thermoplastic elastomer

[0207] According to the method described in Rubber Chem. Technol., 45, 1295 (1972), the block copolymer is reacted with ozone and reduced with lithium aluminum hydride, thereby decomposing the isoprene polymer block of the block copolymer. Specifically, the following steps are followed. That is, in a reaction vessel to which 100 ml of molecular sieve-treated dichloromethane is added, 300 mg of the sample is dissolved. After the reaction vessel is placed in a cooling tank to -25 ° C, oxygen is circulated in the reaction vessel at a flow rate of 170 ml / min, while ozone generated by an ozone generator is introduced. After 30 minutes from the start of the reaction, the reaction is confirmed to be terminated by introducing the gas flowing out of the reaction vessel into an aqueous potassium iodide solution. Next, 50 ml of diethyl ether and 470 mg of lithium aluminum hydride are added to another reaction vessel that has been replaced with nitrogen, and the solution reacted with ozone is slowly added dropwise to the reaction vessel while cooling the reaction vessel with ice water. Then, the reaction vessel is placed in a water bath, slowly heated, and refluxed at 40 ° C for 30 minutes. Then, dilute hydrochloric acid is added dropwise in a reaction vessel while stirring the solution, and the addition is continued until the generation of hydrogen is hardly confirmed. After the reaction, the solid product generated in the solution is separated by filtration, and the solid product is extracted for 10 minutes using 100 ml of diethyl ether. The extract is combined with the filtrate during filtration, and the solvent is distilled off to obtain a solid sample. According to the above-mentioned method for determining the weight average molecular weight, the weight average molecular weight of the sample thus obtained is measured, and this value is used as the weight average molecular weight of the styrene polymer block.

[0208] (4) Weight average molecular weight of the isoprene polymer block constituting the block copolymer of the conjugated diene-aromatic vinyl-based thermoplastic elastomer

[0209] The weight average molecular weight of the isoprene polymer block was determined based on the calculated value by subtracting the weight average molecular weight of the corresponding styrene polymer block determined as above from the weight average molecular weight of the block copolymer determined as above.

[0210] (5) Styrene unit content of the block copolymer constituting the conjugated diene-aromatic vinyl-based thermoplastic elastomer

[0211] It was determined based on the detection intensity ratio of the differential refractometer and the ultraviolet detector in the above-mentioned high performance liquid chromatography measurement. In addition, copolymers having different styrene unit contents were prepared in advance, and these were used to prepare a calibration curve.

[0212] (6) Vinyl bond content of the isoprene polymer block constituting the conjugated diene-aromatic vinyl-based thermoplastic elastomer block copolymer

[0213] It was determined based on proton NMR measurement.

[0214] (7) Styrene unit content of conjugated diene-aromatic vinyl-based thermoplastic elastomer

[0215] It was determined based on proton NMR measurement.

[0216] (8) Melt index of conjugated diene-aromatic vinyl-based thermoplastic elastomer

[0217] The measurement was carried out in accordance with ASTM D1238 (G condition, 200° C., 5 kg load).

[0218] (9) Volume average particle size of colored resin particles (Dv)

[0219] About 0.1 g of the colored resin particles were weighed and placed in a beaker, and 0.1 mL of a surfactant solution (manufactured by FUJIFILM Corporation, trade name: Drywell) as a dispersant was added. 10 to 30 mL of Isoton II was further added to the beaker, and after dispersion for 3 minutes using a 20 W ultrasonic disperser, the volume average particle size (Dv) of the colored resin particles was measured using a particle size measuring machine (manufactured by BECKMAN COULTER CO., Ltd., trade name: Multisizer) under the conditions of aperture: 100 μm, medium: Isoton II, and number of particles to be measured: 100,000.

[0220] (10) Gel content of colored resin particles

[0221] 1.0 g of the colored resin particles were weighed and added to a Soxhlet extractor containing a cylindrical filter paper (manufactured by Cybernavi Inc.: No. 86R, size 28×100 mm), and 100 ml of tetrahydrofuran (THF) was used as a solvent, and refluxed for 5 hours to obtain an extract. THF was distilled off from the extract to obtain a non-volatile component, which was then vacuum dried at 50° C. for 1 hour, accurately weighed, and calculated according to the following calculation formula.

[0222] THF insoluble content (%) = [(TS) / (T)] × 100

[0223] T: Colored resin particle sample amount (g)

[0224] S: Extraction non-volatile content (g)

[0225] (11) Weight average molecular weight (Mw) of colored resin particles

[0226] After adding 0.1g of finely weighed colored resin particles to 100mL glass sample bottles, 49.9g of tetrahydrofuran (THF) was added respectively. Then, a stirrer was placed, and after stirring at room temperature for 1 hour using a magnetic stirrer, a 0.2μm PTFE filter was used to filter to obtain a THF solution of colored resin particles. Finally, 100μL of THF solution was injected into the GPC measuring device respectively. The weight-average molecular weight (Mw) was converted based on the standard curve obtained from the obtained GPC dissolution curve according to the commercially available monodisperse standard polystyrene.

[0227] (GPC measurement conditions)

[0228] GPC: HLC-8220 (manufactured by Tosoh Corporation)

[0229] Column: 2 TSK-GEL MULTIPORE HXL-M (Tosoh Corporation) connected in series

[0230] Eluent: THF

[0231] Flow rate: 1.0mL / min

[0232] Temperature: 40℃

[0233] (12) Melting temperature of colored resin particles (T1 / 2)

[0234] The melting temperature (T1 / 2) of the colored resin particles based on the 1 / 2 method is calculated from the melt viscosity using a flow tester. Specifically, the melt viscosity is measured using a flow tester (manufactured by Shimadzu Corporation, trade name: CFT-500C) under the conditions of a predetermined starting temperature, heating rate, preheating time, and shear stress. Then, the melting temperature (T1 / 2) is calculated using the 1 / 2 method based on the obtained melt viscosity.

[0235] Measurement start temperature: 40°C, heating rate: 3°C / min, preheating time: 5 min, cylinder pressure: 10kgf / cm 2 , mold diameter: 0.5mm, mold length: 1.0mm

[0236] (13) Average value of aspect ratio of the crystal domains of the release agent, average major axis, average minor axis, number of crystal domains of the release agent with aspect ratios in the range of 2 to 10, number of crystal domains of the release agent with aspect ratios in the range of 3 to 8

[0237] The colored resin particles are dispersed in the epoxy resin and solidified, and after cooling to a temperature of -80°C, they are cut using a microtome to prepare a thin slice. Then, the prepared thin slice is stained with a 0.5% concentration of ruthenium tetroxide aqueous solution vapor for about 5 minutes, and the stained thin slice is observed using a transmission electron microscope (TEM). In addition, when preparing the thin slice as the measurement sample, the concentration of the colored resin particles in the thin slice is prepared to be a concentration that can observe 5 to 10 cross sections within a range of 28μm×35μm (magnification 5000 to 6000 times). Then, a measurement image within a field of view of 28μm×35μm is obtained, and in the obtained measurement image, the colored resin particles that do not show the complete image of the cross section of the colored resin particles and the colored resin particles outside the range of 0.6 to 1.2 times relative to the volume average particle size (Dv) are excluded from the evaluation, and on this basis, 5 or more colored resin particles are designated as evaluation objects. Then, the number of crystal domains of the release agent of the specified colored resin particles, the aspect ratio, the major axis and the minor axis of the crystal domains of the release agent are calculated by image analysis, and the calculated results are used to obtain the average value of the aspect ratio, the average major axis and the average minor axis of the crystal domains of the release agent, and the number of crystal domains of the release agent with an aspect ratio in the range of 2 to 10 and the number of crystal domains of the release agent with an aspect ratio in the range of 3 to 8 in the field of view of 2 μm×2 μm square. In addition, the number of crystal domains of the release agent with an aspect ratio in the range of 2 to 10 and the number of crystal domains of the release agent with an aspect ratio in the range of 3 to 8 are obtained by converting the above calculation results into the number of crystal domains in the field of view of 2 μm×2 μm square.

[0238] (14) Storage modulus G'(60) of colored resin particles at 60°C, storage modulus G'(100) at 100°C

[0239] Will be in The colored resin particles are sandwiched between a pair of plates (parallel plates or cross plates) with a load of 20 g (when the colored resin particles are A sample in which the colored resin particles are uniformly arranged over an area and are sandwiched by a pair of plates with a load of 20 g) was used as a measurement sample, and the dynamic viscoelasticity was measured by using a dynamic viscoelasticity measuring device of a rotational plane rheometer (product name "ARES-G2", manufactured by TA Instruments) at a measurement frequency of 24 Hz, a load of 20 g, a heating rate of 5°C / min, and a range of 45 to 150°C to obtain the dynamic viscoelasticity.

[0240] (15) Evaluation of the storage stability of toner

[0241] 10 g of toner is added to a 100 mL polyethylene container, which is sealed. The container is then immersed in a thermostatic water bath set to a specified temperature and taken out after 8 hours. The toner is transferred from the container to a 42-mesh sieve in a manner that does not vibrate as much as possible and placed on a powder tester (manufactured by Hosokawa Micron Group, trade name: Powder Tester PT-R). The amplitude of the sieve is set to 1.0 mm. After the sieve is vibrated for 30 seconds, the mass of the toner remaining on the sieve is measured and taken as the mass of the condensed toner. The highest temperature (°C) at which the mass of the condensed toner becomes less than 0.5 g is taken as the storage temperature, which is taken as an indicator of storage.

[0242] (16) Minimum fixing temperature of toner

[0243] A commercially available non-magnetic single-component developing printer (printing speed 20ppm) was modified so that the temperature of its fixing roller could be changed, and a fixing test was performed using the printer. The fixing test was performed as follows: full black (printing density 100%) printing was performed, the temperature of the fixing roller of the modified printer was changed at intervals of 5°C, the fixing rate of the toner at each temperature was measured, and the relationship between temperature and fixing rate was calculated. The tape was peeled off in the full black (printing density 100%) printing area, and the fixing rate was calculated based on the ratio of the image density before and after the tape was peeled off. That is, when the image density before the tape was peeled off was set to ID (front) and the image density after the tape was peeled off was set to ID (back), the fixing rate can be calculated by the following calculation formula.

[0244] Fixing rate (%) = (ID (after) / ID (before)) × 100

[0245] Here, the tape peeling operation refers to a series of operations of sticking an adhesive tape (Sumitomo 3M Limited, trade name: Scotch Mending Tape 810-3-18) on the measurement part of the test paper, pressing it with a certain pressure to make it adhere, and then peeling the adhesive tape in the direction of the paper at a certain speed. In addition, the image density was measured using a reflection type image densitometer (Macbeth Corporation, trade name: RD914).

[0246] In this fixing test, the lowest fixing roller temperature at which the fixing rate exceeds 80% is defined as the lowest fixing temperature of the toner.

[0247] (17) Thermal offset temperature of toner

[0248] A commercially available non-magnetic single-component development printer (printing speed 20 ppm) was modified so that the temperature of its fixing roller section could be changed, and a heat offset test was conducted using the printer. The heat offset test was conducted as follows: the temperature of the fixing roller section was changed from 150°C to 220°C at intervals of 5°C, a 5 cm square full black image was printed on paper (manufactured by Xerox Corporation, trade name: Vitarity), and the presence of toner fusion on the fixing roller was visually observed to observe whether there was a heat offset phenomenon.

[0249] In this hot offset test, the lowest set temperature at which toner fusion occurs on the fixing roller is defined as the hot offset occurrence temperature.

[0250] (18) Charge amount of toner

[0251] Regarding the charge amount (μC / g) of the toner, an ink cartridge filled with toner that had been left for one day under a normal temperature and humidity environment (23°C, 50% RH) was installed in a commercially available non-magnetic single-component developing printer (printing speed 20 ppm) and evaluated under a normal temperature and humidity environment (23°C, 50% RH). First, two sheets of full white printing were performed, and then the charge amount (μC / g) of the toner attached to the developing roller was measured using an attraction-type charge amount measuring device (manufactured by TREK JAPAN, product name: 210HS-2A). The charge amount of the toner was evaluated for Examples 4-1 to 4-4 and Comparative Examples 4-1 to 4-3.

[0252] (19) Exudation rate

[0253] The toner was stored at a temperature of 40°C for 30 days, and the exudation rate of the toner after storage was measured. Specifically, the toner after storage for 30 days was observed using SEM, and the presence or absence of exudation of the release agent was evaluated for about 100 toner particles, and the ratio of the toner particles that had exuded was taken as the exudation rate (unit: %). The exudation rate was evaluated for Examples 4-1 to 4-4 and Comparative Examples 4-1 to 4-3.

[0254] (20) Ejection evaluation

[0255] A commercially available non-magnetic single-component developing printer (printing speed 20ppm) was used to fill the toner cartridge of the developing device with toner. The toner cartridge filled with toner was then placed at 40°C for 30 days. Then, the removed toner cartridge was installed in the printer and continuous printing was performed at a temperature of 32.5°C and a humidity of 80%. Printing was performed with a halftone image density of 30%. Then, after the start of continuous printing, it was confirmed every hour whether the toner cartridge sprayed toner onto the printed paper (whether there were spots of 0.3×0.3mm or more caused by the toner on the halftone). It can be considered that the longer the time during which the toner cartridge was not confirmed to spray toner onto the printed paper, the higher the spray suppression effect. The spraying was evaluated for Examples 4-1 to 4-4 and Comparative Examples 4-1 to 4-3.

[0256] (21) Scraper attachment

[0257] A commercially available non-magnetic single-component developing printer (printing speed 20 ppm) was used to fill the toner cartridge of the developing device with toner, and the toner cartridge filled with toner was left at 40°C for 30 days to confirm whether there was any attachment on the scraper (scraper for defining the toner layer). The scraper attachment was evaluated for Examples 4-1 to 4-4 and Comparative Examples 4-1 to 4-3.

[0258] [Production Example 1]

[0259] 23.2 kg of cyclohexane, 1.5 mmol of N,N,N',N'-tetramethylethylenediamine (hereinafter referred to as TMEDA) and 1.70 kg of styrene were added to a pressure-resistant reactor, stirred at 40 ° C, and 99.1 mmol of n-butyl lithium was added at the same time, the temperature was raised to 50 ° C and polymerized for 1 hour. The polymerization conversion rate of styrene was 100% by mass. Then, while the temperature was controlled to maintain at 50-60 ° C, 6.03 kg of isoprene was continuously added to the reactor over 1 hour. After the addition of isoprene was completed, it was further polymerized for 1 hour to form a styrene-isoprene diblock copolymer B (copolymer B represented by Ar-D). The polymerization conversion rate of isoprene was 100%. Next, 15.0 mmol of dichlorodimethylsilane as a coupling agent was added for a coupling reaction for 2 hours to form a styrene-isoprene-styrene triblock copolymer (copolymer A represented by Ar-D-Ar). Then, 198 mmol of methanol as a polymerization terminator was added, mixed thoroughly, and the reaction was terminated to obtain a reaction solution containing a block copolymer composition (α1). A portion of the obtained reaction solution was taken out to determine the weight average molecular weight, content ratio, and vinyl bond content of each block copolymer and the block copolymer composition as a whole. The results obtained are shown in Table 1. Then, 0.3 parts of 2,6-di-tert-butyl-p-cresol as an antioxidant were added to 100 parts of the reaction solution obtained in this way (containing 30 parts of polymer components) and mixed, and the mixed solution was added dropwise in a small amount to warm water heated to 85-95°C to volatilize the solvent to obtain a precipitate, which was crushed and dried with hot air at 85°C to recover the block copolymer composition (α1). The melt index of the obtained block copolymer composition (α1) was measured, and the results obtained are shown in Table 2. In addition, the solubility of the obtained block copolymer composition (α1) in styrene at a temperature of 40°C was measured, and the result was 20g / 100g.

[0260] [Production Example 2]

[0261] The block copolymer composition (α2) of Production Example 2 was obtained in the same manner as in Production Example 1 except that the amounts of styrene, n-butyllithium, TMEDA, isoprene, dichlorodimethylsilane and methanol were changed as shown in Table 1, and the measurement was performed in the same manner. The measurement results are shown in Table 2. In addition, the solubility of the obtained block copolymer composition (α2) in styrene at a temperature of 40° C. was measured and the result was 20 g / 100 g.

[0262] [Production Example 3]

[0263] The block copolymer composition (α3) of Production Example 3 was obtained in the same manner as in Production Example 1 except that the amounts of styrene, n-butyllithium, TMEDA, isoprene, dichlorodimethylsilane and methanol were changed as shown in Table 1, and the measurement was performed in the same manner. The measurement results are shown in Table 2. In addition, the solubility of the obtained block copolymer composition (α3) in styrene at a temperature of 40° C. was measured and the result was 20 g / 100 g.

[0264] [Production Example 4]

[0265] The block copolymer composition (α4) of Production Example 4 was obtained in the same manner as in Production Example 1 except that the amounts of styrene, n-butyllithium, TMEDA, isoprene, dichlorodimethylsilane and methanol were changed as shown in Table 1, and the measurement was performed in the same manner. The measurement results are shown in Table 2. In addition, the solubility of the obtained block copolymer composition (α4) in styrene at a temperature of 40° C. was measured and the result was 4 g / 100 g.

[0266] [Production Example 5]

[0267] The block copolymer composition (α5) of Production Example 5 was obtained in the same manner as in Production Example 1 except that the amounts of styrene, n-butyl lithium, TMEDA, isoprene and methanol were changed as shown in Table 1, and tetramethoxysilane was used in the amount shown in Table 1 instead of dichlorodimethylsilane. The measurement was performed in the same manner as in Production Example 1. The measurement results are shown in Table 2. In addition, the block copolymer composition (α5) obtained in Production Example 5 contains a styrene-isoprene diblock copolymer B (copolymer B represented by Ar-D), a tri-branched styrene-isoprene block copolymer C (represented by (Ar-D) 3 X represented copolymer C) and 4-branched styrene-isoprene block copolymer D (represented by (Ar-D) 4 Copolymer D represented by X). The solubility of the obtained block copolymer composition (α5) in styrene at a temperature of 40° C. was measured and found to be 2 g / 100 g.

[0268] [Manufacturing Example 6, Manufacturing Example of Acrylic Resin]

[0269] 200 parts of toluene were added to the reaction vessel, and after stirring the toluene and fully replacing the reaction vessel with nitrogen, the temperature was raised to 90°C, and then a mixed solution of 95 parts of methyl methacrylate, 4.6 parts of n-butyl acrylate, 0.4 parts of acrylic acid, and 2.8 parts of tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF CORPORATION, trade name: PERBUTYL O) was added dropwise to the reaction vessel over 2 hours. Furthermore, the polymerization was terminated by maintaining the mixture under toluene reflux for 10 hours, and then the solvent was distilled off under reduced pressure. Thus, an acrylic resin (Tg 70°C, acid value 2.5, weight average molecular weight (Mw) 11000) was obtained.

[0270] [Table 1]

[0271] Table 1

[0272]

[0273] [Table 2]

[0274] Table 2

[0275]

[0276] [Example 1-1]

[0277] 77 parts of styrene as a monovinyl monomer, 23 parts of n-butyl acrylate, 7 parts of carbon black (Mitsubishi Chemical Corporation, trade name: #25B) as a colorant, 0.6 parts of divinylbenzene as a crosslinkable polymerizable monomer, 1.2 parts of tert-dodecyl mercaptan as a molecular weight modifier, 0.3 parts of polymethacrylate macromonomer (TOAGOSEI CO., Ltd., trade name: AA6, Tg = 94°C) and 1 part of the acrylic resin obtained in Preparation Example 2 were wet-ground, and then 1 part of a charge control resin as a charge control agent (styrene / acrylic resin containing quaternary ammonium salt as a functional group, copolymerization ratio of monomers containing quaternary ammonium salt functional groups: 2%), 20 parts of behenyl stearate as a release agent (number average molecular weight (Mn): 592) and 5 parts of the block copolymer composition (α1) obtained in Preparation Example 1 as an additive having a polydiene structure were added and mixed to obtain a polymerizable monomer composition.

[0278] On the other hand, in a stirring tank, at room temperature, an aqueous solution of 7.4 parts of magnesium chloride (water-soluble multivalent metal salt) dissolved in 250 parts of ion exchange water is slowly added with stirring to an aqueous solution of 4.1 parts of sodium hydroxide (alkali metal hydroxide) dissolved in 50 parts of ion exchange water to prepare a magnesium hydroxide colloid (poorly soluble metal hydroxide colloid) dispersion.

[0279] On the other hand, 2 parts of methyl methacrylate as a polymerizable monomer for shell and 65 parts of ion exchange water were finely dispersed by an ultrasonic emulsifier to obtain an aqueous dispersion of the polymerizable monomer for shell.

[0280] The polymerizable monomer composition is added to the magnesium hydroxide colloidal dispersion obtained above, and stirred until the droplets are stable. After adding 6 parts of tert-butyl peroxyisobutyrate (manufactured by NOF Corporation, trade name: PERBUTYL IB) as a polymerization initiator, an inline emulsifying disperser (manufactured by Pacific Machinery & Engineering Co., Ltd., trade name: Milder) is used to perform high shear stirring at a speed of 15000 rpm, so that it circulates and disperses to form droplets of the polymerizable monomer composition.

[0281] Next, 1 part of sodium tetraborate decahydrate was added to the aqueous dispersion of the polymerizable monomer composition formed by droplets, and the mixture was placed in a reactor equipped with a stirring blade and heated to 85°C for polymerization reaction. After the polymerization conversion rate reached almost 100%, the aqueous dispersion of the polymerizable monomer for shell prepared above and 0.3 parts of 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)-propionamide) (manufactured by FUJIFILM Wako Pure Chemical Corporation, trade name: VA-086, water-soluble) as a polymerization initiator for shell were added to the reactor. After the polymerization was continued for 4 hours, the reaction was terminated by water cooling, and an aqueous dispersion of colored resin particles with a core-shell structure was obtained.

[0282] The aqueous dispersion of the colored resin particles was washed with dilute sulfuric acid (25°C, 10 minutes) to a pH of 4.5 or less. Next, after separating the water by filtration, 200 parts of ion exchange water were added again, slurried again, and the water washing treatment (washing / filtration / dehydration) was repeated several times at room temperature (25°C). After filtering and separating the solid content, vacuum drying was performed to obtain dried colored resin particles. According to the above method, the obtained colored resin particles were measured for the average value of the aspect ratio of the crystal domains containing the release agent, the average major diameter, the average minor diameter, the number of crystal domains of the release agent with an aspect ratio in the range of 2 to 10, the number of crystal domains of the release agent with an aspect ratio in the range of 3 to 8, the storage modulus G'(60) at 60°C, and the storage modulus G'(100) at 100°C. These results are shown in Table 3.

[0283] In addition, 0.5 parts of silica fine particles with a number average primary particle size of 7 nm hydrophobized by cyclic silazane and 1 part of silica fine particles with a number average primary particle size of 35 nm hydrophobized by amino-modified silicone oil were added as external additives to 100 parts of the colored resin particles obtained above, and mixed and stirred using a high-speed stirrer (manufactured by Nippon Coke & Engineering Co., Ltd., trade name: FM Mixer) to perform external addition treatment to prepare a toner for electrostatic image development. Using the obtained toner for electrostatic image development, the above-mentioned various measurements were performed. The results are shown in Table 2.

[0284] [Example 1-2]

[0285] The same procedure as in Example 1-1 was followed except that 20 parts of stearyl stearate (number average molecular weight (Mn): 536) was used instead of 20 parts of behenyl stearate as a release agent to obtain colored resin particles and an electrostatic image developing toner of Example 1-2, and the results were evaluated in the same manner. The results are shown in Table 3.

[0286] [Examples 1-3]

[0287] The same procedure as in Example 1-1 was followed except that 20 parts of behenyl behenate (number average molecular weight (Mn): 648) was used as a release agent instead of 20 parts of behenyl stearate to obtain colored resin particles and an electrostatic image developing toner of Example 1-3, which were evaluated in the same manner. The results are shown in Table 3.

[0288] [Examples 1-4]

[0289] The same procedures as in Example 1-1 were followed except that 1.7 parts of solution-polymerized polyisoprene rubber 1 (trade name "KURAPRENE LIR-30", manufactured by Kuraray Co., Ltd., weight average molecular weight (Mw): 28,000, solubility in styrene at 40° C.: 16 g / 100 g) was used instead of 5 parts of the block copolymer composition (α1) obtained in Production Example 1 as an additive having a polydiene structure, to obtain colored resin particles and a toner for electrostatic image development of Example 1-4, and the results were evaluated in the same manner. The results are shown in Table 3.

[0290] [Examples 1-5]

[0291] The same procedure as in Example 1-1 was followed except that the amount of the block copolymer composition (α1) as an additive having a polydiene structure was changed from 5 parts to 2 parts to obtain colored resin particles and an electrostatic image developing toner of Example 1-5, which were evaluated in the same manner. The results are shown in Table 3.

[0292] [Examples 1-6]

[0293] The same procedure as in Example 1-1 was followed except that the amount of the block copolymer composition (α1) as an additive having a polydiene structure was changed from 5 parts to 10 parts to obtain colored resin particles and an electrostatic image developing toner of Example 1-6, which were evaluated in the same manner. The results are shown in Table 3.

[0294] [Comparative Example 1-1]

[0295] The colored resin particles and electrostatic image developing toner of Comparative Example 1-1 were obtained in the same manner as in Example 1-1 except that the block copolymer composition (α1) as an additive having a polydiene structure was not added, and were evaluated in the same manner.

[0296] [Comparative Example 1-2]

[0297] The same procedure as in Comparative Example 1-1 was followed except that 20 parts of behenyl behenate (number average molecular weight (Mn): 648) was used as a release agent instead of 20 parts of behenyl stearate to obtain colored resin particles and an electrostatic image developing toner of Comparative Example 1-2, which were evaluated in the same manner. The results are shown in Table 3.

[0298] [Comparative Examples 1-3]

[0299] The same procedures as in Example 1-1 were followed except that 1.7 parts of solution-polymerized polyisoprene rubber 2 (trade name "IR2200", manufactured by Japan Zeon Co., Ltd., weight average molecular weight (Mw): 1100000, solubility in styrene at 40°C: 2.4 g / 100 g) was used instead of 5 parts of the block copolymer composition (α1) obtained in Production Example 1 as an additive having a polydiene structure, to obtain colored resin particles and a toner for electrostatic image development of Comparative Example 1-3, and the results were evaluated in the same manner. The results are shown in Table 3.

[0300] [Table 3]

[0301]

[0302] [Evaluation of Examples 1-1 to 1-6 and Comparative Examples 1-1 to 1-3]

[0303] As shown in Table 3, a polydiene structure-containing additive having a solubility of 3 to 40 g / 100 g in styrene at a temperature of 40° C. is used, and the number of crystal domains of the release agent having an aspect ratio in the range of 2 to 10 in a 2 μm×2 μm square field of view of a cross section observed by a transmission electron microscope (TEM) is 2 to 30, and the storage modulus G'(60) at 60° C. is 1.6×10 8 ~5.0×10 8 The toners of Examples 1-1 to 1-6 obtained using the colored resin particles of Pa as colored resin particles had high storage temperatures, excellent storage stability, low minimum fixing temperatures, and excellent low-temperature fixing properties. In addition, Examples 1-1 to 1-6 also had high hot offset occurrence temperatures and excellent hot offset resistance.

[0304] On the other hand, the toners of Comparative Examples 1-1 to 1-3 obtained using colored resin particles which do not contain an additive having a polydiene structure having a solubility of 3 to 40 g / 100 g in styrene at a temperature of 40° C. and in which the number of crystal domains of a release agent having an aspect ratio in the range of 2 to 10 is less than 2 have low storage temperatures and poor storage stability.

[0305] in addition, Figure 1 (A) is a cross-sectional photograph of the colored resin particles in Example 1-1 obtained by a transmission electron microscope (TEM), Figure 1 (B) is a cross-sectional photograph of the colored resin particles in Comparative Example 1-1 obtained by a transmission electron microscope (TEM). Figure 1As shown in (A), according to Examples 1-1 to 1-6, the crystal domains of the release agent with an aspect ratio in the range of 2 to 10 are finely dispersed in the colored resin particles (the same applies to Examples 2-1 to 2-2, 3-1 to 3-7, and 4-1 to 4-4 described later). In contrast, Figure 1 As shown in (B), in Comparative Examples 1-1 to 1-3, the release agent is locally present near the center of the colored resin particle (near a position slightly lower left from the center), forming a large domain structure.

[0306] [Example 2-1]

[0307] The same procedure as in Example 1-1 was carried out except that the amount of divinylbenzene used was changed from 0.6 part to 0.3 part to obtain colored resin particles and an electrostatic image developing toner of Example 2-1, and the same evaluations were performed.

[0308] [Example 2-2]

[0309] The same procedure as in Example 2-1 was carried out except that the amount of divinylbenzene used was changed from 0.3 part to 0.33 part to obtain colored resin particles and an electrostatic image developing toner of Example 2-2, and the same evaluations were performed.

[0310] [Comparative Example 2-1]

[0311] The same procedure as in Example 2-1 was followed except that the amount of divinylbenzene used was changed from 0.3 parts to 0.51 parts and that the block copolymer composition (α1) as an additive having a polydiene structure was not added to obtain colored resin particles and an electrostatic image developing toner of Comparative Example 2-1, and the results were evaluated in the same manner. The results are shown in Table 4.

[0312] [Comparative Example 2-2]

[0313] The same procedure as in Example 2-1 was followed except that the amount of divinylbenzene used was changed from 0.3 parts to 0.54 parts and that the block copolymer composition (α1) as an additive having a polydiene structure was not added to obtain colored resin particles and an electrostatic image developing toner of Comparative Example 2-2, which were evaluated in the same manner. The results are shown in Table 4.

[0314] [Comparative Example 2-3]

[0315] The same procedures as in Example 2-1 were followed except that the amount of divinylbenzene used was changed from 0.3 parts to 0.6 parts and that 5 parts of a styrene-ethylene / propylene-styrene block copolymer (manufactured by Kuraray Co., Ltd., trade name: SEPTON 2104, styrene unit content: 65% by mass, weight average molecular weight (Mw): 64,000, solubility in styrene at 40° C.: 15 g / 100 g) was used in place of 5 parts of the block copolymer composition (α1) as an additive having a polydiene structure, to obtain colored resin particles and a toner for electrostatic image development of Comparative Example 2-3, and the same evaluations were performed. The results are shown in Table 4.

[0316] [Comparative Examples 2-4]

[0317] The same procedures as in Example 2-1 were followed except that the amount of divinylbenzene used was changed from 0.3 parts to 0.6 parts and that 5 parts of a styrene-ethylene / propylene-styrene block copolymer (manufactured by Kuraray Co., Ltd., trade name: SEPTON 4033, styrene unit content: 30% by mass, weight average molecular weight (Mw): 81000, solubility in styrene at 40°C: 15 g / 100 g) was used in place of 5 parts of the block copolymer composition (α1) as an additive having a polydiene structure, to obtain colored resin particles and a toner for electrostatic image development of Comparative Example 2-4, and the same evaluations were performed. The results are shown in Table 4.

[0318] [Table 4]

[0319]

[0320] [Evaluation of Examples 2-1 to 2-2 and Comparative Examples 2-1 to 2-4]

[0321] As shown in Table 4, a polydiene structure-containing additive having a solubility of 3 to 40 g / 100 g in styrene at a temperature of 40° C. is used, and the number of crystal domains of the release agent having an aspect ratio in the range of 2 to 10 in a 2 μm×2 μm square field of view of a cross section observed by a transmission electron microscope (TEM) is 2 to 30, and the storage modulus G'(60) at 60° C. is 1.6×10 8 ~5.0×10 8 Colored Resin Particles of Pa The toners of Examples 2-1 to 2-2 obtained as colored resin particles had a high storage temperature, excellent storage stability, a low minimum fixing temperature, and excellent low-temperature fixing property.

[0322] On the other hand, the storage modulus G'(60) at 60°C is less than 1.6×10 8The toners of Comparative Examples 2-1 to 2-4 obtained with the colored resin particles of Pa had low storage temperatures and were inferior in storage stability.

[0323] [Example 3-1]

[0324] The same procedure as in Example 1-1 was carried out except that the amount of divinylbenzene used was changed from 0.6 part to 0.45 part to obtain colored resin particles and an electrostatic image developing toner of Example 3-1, and the same evaluations were performed.

[0325] [Example 3-2]

[0326] The same procedure as in Example 3-1 was carried out except that the amount of divinylbenzene used was changed from 0.6 part to 0.3 part to obtain colored resin particles and an electrostatic image developing toner of Example 3-2, which were evaluated in the same manner.

[0327] [Example 3-3]

[0328] The same procedure as in Example 3-1 was followed except that the amount of divinylbenzene used was changed from 0.45 parts to 0.6 parts and the amount of the block copolymer composition (α1) obtained in Production Example 1 was changed from 5 parts to 2 parts to obtain colored resin particles and an electrostatic image developing toner of Example 3-3, and the evaluations were performed in the same manner. The results are shown in Table 5.

[0329] [Examples 3-4]

[0330] The same procedure as in Example 3-3 was carried out except that the amount of divinylbenzene used was changed from 0.6 part to 0.5 part to obtain colored resin particles and an electrostatic image developing toner of Example 3-4, and the same evaluations were performed.

[0331] [Examples 3-5]

[0332] The same procedure as in Example 3-3 was carried out except that the amount of divinylbenzene used was changed from 0.6 part to 0.4 part to obtain colored resin particles and an electrostatic image developing toner of Example 3-5, which were evaluated in the same manner.

[0333] [Examples 3-6]

[0334] The same procedure as in Example 3-1 was followed except that the amount of styrene used was changed from 77 parts to 83 parts, the amount of n-butyl acrylate used was changed from 23 parts to 17 parts, and the amount of divinylbenzene used was changed from 0.45 parts to 0.6 parts to obtain colored resin particles and an electrostatic image developing toner of Example 3-6, and the evaluations were performed in the same manner. The results are shown in Table 5.

[0335] [Examples 3-7]

[0336] The same procedure as in Example 3-3 was repeated except that the acrylic resin obtained in Production Example 2 was not added to obtain colored resin particles and an electrostatic image developing toner of Example 3-7, which were evaluated in the same manner.

[0337] [Comparative Example 3-1]

[0338] The colored resin particles and electrostatic image developing toner of Comparative Example 3-1 were obtained in the same manner as in Example 3-3 except that the block copolymer composition (α1) obtained in Production Example 1 was not used, and were evaluated in the same manner.

[0339] [Comparative Example 3-2]

[0340] The same procedures as in Example 3-3 were followed except that 2 parts of a styrene-ethylene / propylene block copolymer (manufactured by Kuraray Co., Ltd., trade name: SEPTON 2063, styrene unit content: 13% by mass, weight average molecular weight (Mw): 91,000, solubility in styrene at 40° C.: 15 g / 100 g) were used instead of 5 parts of the block copolymer composition (α1) obtained in Production Example 1 to obtain colored resin particles and a toner for electrostatic image development of Comparative Example 3-2, and the results were evaluated in the same manner. The results are shown in Table 5.

[0341] [Comparative Example 3-3]

[0342] The same procedure as in Example 3-3 was followed except that 5 parts of a styrene-ethylene / propylene block copolymer (manufactured by Kuraray Co., Ltd., trade name: SEPTON 2063) was used instead of 5 parts of the block copolymer composition (α1) obtained in Production Example 1 to obtain colored resin particles and a toner for electrostatic image development of Comparative Example 3-3, and the same evaluation was performed. The results are shown in Table 5.

[0343] [Comparative Examples 3-4]

[0344] The same procedure as in Example 3-3 was followed except that 2 parts of a styrene-ethylene / propylene-styrene block copolymer (manufactured by Kuraray Co., Ltd., trade name: SEPTON 2104) was used in place of 5 parts of the block copolymer composition (α1) obtained in Production Example 1 to obtain colored resin particles and a toner for electrostatic image development of Comparative Example 3-4, and the results were evaluated in the same manner. The results are shown in Table 5.

[0345] [Comparative Examples 3-5]

[0346] The same procedures as in Example 3-3 were followed except that 2 parts of a styrene-ethylene / propylene-styrene block copolymer (manufactured by Kuraray Co., Ltd., trade name: SEPTON 4033) was used in place of 5 parts of the block copolymer composition (α1) obtained in Production Example 1 to obtain colored resin particles and a toner for electrostatic image development of Comparative Example 3-5, and the same evaluations were performed. The results are shown in Table 5.

[0347] [Table 5]

[0348]

[0349] [Evaluation of Examples 3-1 to 3-7 and Comparative Examples 3-1 to 3-5]

[0350] As shown in Table 5, a polydiene structure-containing additive having a solubility of 3 to 40 g / 100 g in styrene at a temperature of 40° C. is used, and the number of crystal domains of the release agent having an aspect ratio in the range of 2 to 10 in a 2 μm×2 μm square field of view of a cross section observed by a transmission electron microscope (TEM) is 2 to 30, and the storage modulus G'(60) at 60° C. is 1.6×10 8 ~5.0×10 8 Colored Resin Particles of Pa The toners of Examples 3-1 to 3-7 obtained as colored resin particles had high storage temperatures, excellent storage stability, low minimum fixing temperatures, and excellent low-temperature fixing properties.

[0351] On the other hand, the toners of Comparative Examples 3-1 to 3-5, which did not contain an additive having a polydiene structure or used an aromatic vinyl-based thermoplastic elastomer having no polydiene structure and thus no unsaturated bond capable of polymerization, had low storage temperatures and poor storage stability. In addition, the presence of behenyl stearate as a release agent in the toners of Comparative Examples 3-1 to 3-5 was confirmed by cross-sectional SEM and TEM, and it was confirmed that behenyl stearate was localized near the center of the toner particles, forming a large crystal domain structure.

[0352] [Example 4-1]

[0353] 70.5 parts of styrene and 29.5 parts of n-butyl acrylate as monovinyl monomers, 7 parts of carbon black (Mitsubishi Chemical Corporation, trade name: #25B) as a colorant, 0.6 parts of divinylbenzene as a crosslinking polymerizable monomer, 1.2 parts of tert-dodecyl mercaptan as a molecular weight modifier, 0.3 parts of polymethacrylate macromonomer (TOAGOSEI CO., Ltd., trade name: AA6, Tg = 94°C) and 1 part of the acrylic resin obtained in Preparation Example 6 are wet-ground, and then 1 part of a charge control resin as a charge control agent (styrene / acrylic resin containing quaternary ammonium salt as a functional group, copolymerization ratio of monomers containing quaternary ammonium salt functional groups: 2%), 20 parts of behenyl stearate as a release agent (number average molecular weight (Mn): 592) and 5 parts of the block copolymer composition (α2) obtained in Preparation Example 2 as an aromatic vinyl-based thermoplastic elastomer are added and mixed to obtain a polymerizable monomer composition.

[0354] Then, the colored resin particles and electrostatic image developing toner of Example 4-1 were obtained in the same manner as in Example 1-1 except that the polymerizable monomer composition obtained above was used, and were evaluated in the same manner.

[0355] [Example 4-2]

[0356] The same procedure as in Example 4-1 was followed except that 5 parts of the block copolymer composition (α1) obtained in Production Example 1 were used in place of 5 parts of the block copolymer composition (α2) obtained in Production Example 2 to obtain colored resin particles and an electrostatic image developing toner of Example 4-2, and the same evaluations were performed. The results are shown in Table 6.

[0357] [Example 4-3]

[0358] The same procedure as in Example 4-1 was followed except that 5 parts of the block copolymer composition (α3) obtained in Production Example 3 were used in place of 5 parts of the block copolymer composition (α2) obtained in Production Example 2 to obtain colored resin particles and an electrostatic image developing toner of Example 4-3, and the same evaluations were performed. The results are shown in Table 6.

[0359] [Example 4-4]

[0360] The same procedure as in Example 4-1 was followed except that 5 parts of the block copolymer composition (α1) obtained in Preparation Example 1 was used in place of 5 parts of the block copolymer composition (α2) obtained in Preparation Example 2, and that the low molecular weight acrylic resin obtained in Preparation Example 6 was not used, to obtain the colored resin particles and electrostatic image developing toner of Example 4-4, and the evaluations were performed in the same manner. The results are shown in Table 6.

[0361] [Comparative Example 4-1]

[0362] The colored resin particles and electrostatic image developing toner of Comparative Example 4-1 were obtained in the same manner as in Example 4-1 except that the block copolymer composition (α2) obtained in Production Example 2 was not used, and were evaluated in the same manner.

[0363] [Comparative Example 4-2]

[0364] The same procedure as in Example 4-1 was followed except that 5 parts of the block copolymer composition (α4) obtained in Production Example 4-2 were used in place of 5 parts of the block copolymer composition (α2) obtained in Production Example 2 to obtain colored resin particles and an electrostatic image developing toner of Comparative Example 4-2, and the evaluations were performed in the same manner. The results are shown in Table 6.

[0365] [Comparative Example 4-3]

[0366] The same procedure as in Example 4-1 was followed except that 5 parts of the block copolymer composition (α5) obtained in Production Example 5 were used in place of 5 parts of the block copolymer composition (α2) obtained in Production Example 2 to obtain colored resin particles and an electrostatic image developing toner of Comparative Example 4-3, and the evaluations were performed in the same manner. The results are shown in Table 6.

[0367] [Table 6]

[0368]

[0369] As shown in Table 6, it was confirmed that the toners of Examples 4-1 to 4-4 obtained by using colored resin particles further containing an aromatic vinyl-based thermoplastic elastomer containing a diblock copolymer composed of an aromatic vinyl polymer block and a polymer block copolymerizable with the aromatic vinyl polymer in a ratio of 40% by weight or more as an additive having a polydiene structure had the characteristics of high storage temperature, excellent storage stability, low minimum fixing temperature, and excellent low-temperature fixing property, and in addition, had high charging properties, could suppress the bleeding of the release agent, and could effectively suppress the ejection and adhesion to the blade under high temperature and high humidity conditions.

[0370] On the other hand, the toners of Comparative Examples 4-1 to 4-3, which used a diblock copolymer that did not contain an aromatic vinyl polymer block and a polymer block copolymerizable with an aromatic vinyl polymer, or used an aromatic vinyl-based thermoplastic elastomer in which the diblock copolymer contained less than 40 wt %, experienced ejection and adhesion to the scraper under high temperature and high humidity conditions.

Claims

1. A toner for electrostatic image development, comprising colored resin particles, wherein the colored resin particles contain a binder resin, a colorant, a charge control agent, a release agent, and an additive having a polydiene structure, The additive having a polydiene structure has a solubility of 3 to 40 g / 100 g in styrene at a temperature of 40° C. and is a conjugated diene-aromatic vinyl-based thermoplastic elastomer, wherein the conjugated diene-aromatic vinyl-based thermoplastic elastomer contains a diblock copolymer in a ratio of 40% by mass or more, wherein the diblock copolymer is formed by a block of an aromatic vinyl polymer and a block of a polymer copolymerizable with the aromatic vinyl polymer, When the cross section of the colored resin particles is observed by a transmission electron microscope (TEM), the number of crystal domains of the release agent having an aspect ratio in the range of 2 to 10 is 2 to 30 in a 2 μm×2 μm square field of view of the cross section of the colored resin particles.

2. A toner for electrostatic image development, comprising colored resin particles, wherein the colored resin particles contain a binder resin, a colorant, a charge control agent, a release agent, and an additive having a polydiene structure, The additive having a polydiene structure has a solubility of 3 to 40 g / 100 g in styrene at a temperature of 40° C. and is a conjugated diene-aromatic vinyl-based thermoplastic elastomer, wherein the conjugated diene-aromatic vinyl-based thermoplastic elastomer contains a diblock copolymer in a ratio of 40% by mass or more, wherein the diblock copolymer is formed by a block of an aromatic vinyl polymer and a block of a polymer copolymerizable with the aromatic vinyl polymer, The storage modulus G'(60) of the colored resin particles at 60°C obtained by dynamic viscoelasticity measurement was 1.6×10 8 ~5.0×10 8 Pa.

3. The electrostatic image developing toner according to claim 1, wherein The storage modulus G'(60) of the colored resin particles at 60°C obtained by dynamic viscoelasticity measurement was 1.6×10 8 ~5.0×10 8 Pa.

4. The electrostatic image developing toner according to claim 2 or 3, wherein The storage modulus G'(100) of the colored resin particles at 100°C obtained by dynamic viscoelasticity measurement is 1.0×10 5 ~3.0×10 5 Pa.

5. The electrostatic image developing toner according to claim 2 or 3, wherein The ratio of the storage modulus G'(60) of the colored resin particles at 60°C to the storage modulus G'(100) at 100°C, G'(60) / G'(100), obtained by dynamic viscoelasticity measurement, is 1.0×10 3 ~5.0×10 3 .

6. The electrostatic image developing toner according to claim 1 or 2, wherein The content ratio of the aromatic vinyl monomer unit in the conjugated diene-aromatic vinyl-based thermoplastic elastomer is 10 to 30% by mass based on the total monomer units.

7. The electrostatic image developing toner according to claim 1 or 2, wherein The content of the additive having a polydiene structure is 1 to 10 parts by mass relative to 100 parts by mass of the binder resin.

8. The electrostatic image developing toner according to claim 1 or 2, wherein The release agent is a fatty acid ester compound with a number average molecular weight (Mn) of 500-1500.

9. The electrostatic image developing toner according to claim 1 or 2, wherein The electrostatic image developing toner further contains an acrylic resin.

Citation Information

Patent Citations

  • toner

    JP2012177914A

  • Black toner

    JP2019012188A

  • Electrostatic charge image developing toner

    JP2004258429A

  • Electrostatic charge image developing toner

    JP2010085841A